10-year Characteristics of Moisture Source Regions and Their Potential Effect on Seasonal Isotopic Signatures of delta O-18 in Tropical Trees of Southern Ecuador - Landshuter, Nadja; Mölg, Thomas; Grießinger, Jussi; Bräuning, Achim; Peters, Thorsten (Frontiers in Earth Science, 2020)
Ratios of stable oxygen isotopes in tree rings (delta O-18) are a valuable proxy for reconstructing past climates. Such reconstructions allow us to gain better knowledge of climate dynamics under different (eg warmer) environmental conditions, which also forms the basis for effective risk management. The latter aspect is particularly relevant for our study site on the western flanks of the Andes in Southern Ecuador, since the region is frequently affected by droughts and heavy precipitation events during the rainy season (January to April), leading to enormous social and economic losses. In particular, we focus on precipitation amounts and moisture source regions as they are known to influence the delta O-18 signature of tree rings. Moisture source regions are based on 240 h backward trajectories that were calculated with the trajectory model LAGRANTO for the rainy seasons 2008 to 2017. A moisture source diagnostic was applied to the air parcel pathways. The resulting moisture source regions were analyzed by calculating composites based on precipitation amounts, season, and calendar year. The precipitation amounts were derived from data of a local Automatic Weather Station (AWS). The analysis confirms that our study site receives its moisture both, from the Atlantic and the Pacific Oceans. Heavy precipitation events are linked to higher moisture contributions from the Pacific, and local SST anomalies along the coast of Ecuador are of higher importance than those off the coast toward the central Pacific. Moreover, we identified increasing moisture contributions from the Pacific over the course of the rainy season. This change and also rain amount effects are detectable in preliminary data of delta O-18 variations in tree rings of Bursera graveolens. These signatures can be a starting point for investigating atmospheric and hydroclimatic processes, which trigger delta O-18 variations in tree rings, more extensively in future studies.
CRIS-Team WoS Importer:2021-02-26

501 years of spring precipitation history for the semi-arid Northern Iran derived from tree-ring δ18O data - Foroozan, Zeynab; Grießinger, Jussi; Pourtahmasi, Kambiz; Bräuning, Achim (Atmosphere, 2020)
In semi-arid regions of the world, knowledge about the long-term hydroclimate variability is essential to analyze and evaluate the impact of current climate change on ecosystems. We present the first tree-ring δ18O based hydroclimatic reconstruction for northern semi-arid Iran spanning the period 1515-2015. A highly significant correlation between tree-ring δ18O variations of juniper trees and spring (April-June) precipitation reveals a major influence of spring water availability during the early growing season. The driest period of the past 501 years occurred in the 16th century while the 18th century was the wettest, during which the overall highest frequency of wet year events occurred. A gradual decline in spring precipitation is evident from the beginning of the 19th century, pointing to even drier climate conditions. The analysis of dry/wet events indicates that the frequency of years with relatively dry spring increased over the last three centuries, while the number of wet events decreased. Our findings are in accordance with historical Persian disaster records (e.g., the severe droughts of 1870-1872, 1917-1919; severe flooding of 1867, the 1930s, and 1950). Correlation analyses between the reconstruction and different atmospheric circulation indices revealed no significant influence of large-scale drivers on spring precipitation in northern Iran.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Climate extremes; Climate reconstruction; Juniperus polycarpos; Paleohydroclimatic proxy; Stable isotope dendroclimatology; δ

800 years of tree-ring δ18O reflect variability of precipitation in southeastern Tibet - Grießinger, Jussi; Bräuning, Achim; Helle, Gerhard; Thomas, Axel; Schleser, Gerhard Hans (TRACE - Tree Rings in Archaeology, Climatology and Ecology, Vol. 7: Proceedings of the DENDROSYMPOSIUM 2008 Scientific Technical Report STR 09/03, GFZ Potsdam, 2009)
UnivIS-Import:2015-03-09:Pub.2009.nat.dgeo.IG.LGIPDT.800yea

A dual stable isotope approach unravels common climate signals and species-specific responses to environmental change stored in multi-century tree-ring series from the Tibetan plateau - Grießinger, Jussi; Bräuning, Achim; Helle, Gerhard; Schleser, Gerhard Hans; Hochreuther, Philipp; Meier, Wolfgang; Zhu, Haifeng (Geosciences, 2019)
Tree-rings are recorders of environmental signals and are therefore often used to reconstruct past environmental conditions. In this paper, we present four annually resolved, multi-centennial tree-ring isotope series from the southeastern Tibetan plateau. The investigation site, where juniper and spruce trees jointly occur, is one of the highest known tree-stands in the world. Tree ring cellulose oxygen (δ 18 O) and carbon (δ 13 C) isotopes were analyzed for a common period of 1685–2007 AD to investigate climate–isotope relationships. Therefore, various climate parameters from a local meteorological station and from the CRU 4.02 dataset were used. Tree-ring δ 18 O of both species revealed highly significant sensitivities with a high degree of coherence to hydroclimate variables during the growing season. The obtained δ 18 O–climate relationships can even be retained using a species mean. In contrast, the individual δ13C series indicated a weaker and non-uniform response to the tested variables. Underlying species-specific responses and adaptations to the long-term trend in atmospheric CO 2 bias even after a trend correction identified dominant environmental factors triggering the tree-ring δ 13 C at our site. However, analysis of individual intrinsic water-use efficiency in juniper and spruce trees indicated a species-specific adaptation strategy to climate change.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Intrinsic water-use efficiency (iWUE); Juniperus tibetica; Multi-centennial isotope time-series; Picea balfouriana; Tibetan plateau; tree-ring δ18O; tree-ring δ13C

Ages of major Little Ice Age glacier fluctuations on the southeast Tibetan Plateau derived from tree-ring-based moraine dating - Hochreuther, Philipp; Loibl, David; Wernicke, Jakob; Zhu, Haifeng; Grießinger, Jussi; Bräuning, Achim (Palaeogeography, Palaeoclimatology, Palaeoecology, 2015)
Advances and retreats of glaciers on the Tibetan Plateau (TP) are widely regarded as indicators for climate changes sensitive to macroclimatic forcing mechanisms like the Asian summer monsoon. However, it often remains unclear why some glaciers retreat or advance earlier than others, particularly regarding the timing of the so-called ‘Little Ice Age (LIA) maximum’. Within this study, we present newly acquired tree-ring data from four glacier forefields in the Nyainqêntanglha Range on the southeastern TP and link them to previous studies. Two of the glaciers formed a double-tongue moraine set during the LIA, with trees providing minimum ages for two different major glacier extents. In combination with evidence from a third glacier, three warm phases within the generally cold LIA can be deduced during the first half of the 16th century, and the mid-17th and 18th centuries. This implies the occurrence of three preceding major cold spells. A minor cool phase between 1790 and 1850 marks the end of the LIA on the southeast TP. Minimum ages for beginning retreat from the last major LIA glacial advance differ by only 40 years for all sampled monsoonal temperate valley glaciers in the Nyainqêntanglha Range. This implies a common forcing, whose impact on glacier dynamics is only slightly altered by topographical factors or local climatic conditions. Regression analysis suggests that the delay of the glacier retreat from the maximum extent is mainly related to glacier size, with minor influence of ablation area aspect. All moraine ages highlight intermediate LIA warm phases on the southeast TP corresponding to warm phases on the northern Hemisphere and thus prove monsoonal temperate glaciers to be highly sensitive archives for northern hemispheric climatic conditions.
Keywords: Dendroglaciology; Tibetan Plateau; Glacier history; Tree rings; Moraine dating

Air mass origin signals in δ 18O of tree-ring cellulose revealed by back-trajectory modeling at the monsoonal Tibetan plateau - Wernicke, Jakob; Hochreuther, Philipp; Grießinger, Jussi; Zhu, Haifeng; Wang, Lily; Bräuning, Achim (International Journal of Biometeorology, 2017)
Keywords: Backward trajectory; Tibetan plateau; Asian summer monsoon; Tree-ring δ18O

Air mass signals in δ18O of tree-ring cellulose revealed by back-trajectory modeling at the monsoonal Tibetan plateau - Wernicke, Jakob; Hochreuther, Philipp; Grießinger, Jussi; Zhu, Haifeng; Wang, Lily; Bräuning, Achim (International Journal of Biometeorology, 2017)
A profound consideration of stable oxygen isotope source water origins is a precondition for an unambiguous palaeoenvironmental interpretation of terrestrial δ18O archives. To stress the influence of air mass origins on widely used δ18O tree-ring chronologies, we conducted correlation analyses between six annually resolved δ18O tree-ring cellulose (δ18OTC) chronologies and mean annual air package origins obtained from backward trajectory modeling. This novel approach has been tested for a transect at the southeastern Tibetan plateau (TP), where air masses with different isotopic composition overlap. Detailed examinations of daily precipitation amounts and monthly precipitation δ18O values (δ18OP ) were conducted with the ERA Interim and Laboratoire de M´et´eorologie Dynamique General Circulation Model (LMDZiso) data, respectively. Particularly the southernmost study sites are influenced by a distinct amount effect. Here, air package origin δ18OTC relations are generally weaker in contrast to our northern located study sites. We found that tree-ring isotope signatures at dry sites with less rain days per year tend tobe influenced stronger by air mass origin than tree-ringisotope values at semi-humid sites. That implies that the local hydroclimate history inferred from δ18OTC archives is better recorded at semi-humid sites.
Keywords: Tree-ring δ18O; Backward trajectory; Asian summer monsoon; Tibetan plateau

Air moisture signals in a stable oxygen isotope chronology of dwarf shrubs from the central Tibetan Plateau - Wernicke, Jakob; Stark, Georg; Wang, Lily; Grießinger, Jussi; Bräuning, Achim (Annals of Botany, 2019)
BACKGROUND AND AIMS: Annually resolved biological climate proxies beyond the altitudinal and latitudinal distribution limit of trees are rare. In such regions, several studies have demonstrated that annual growth rings of dwarf shrubs are suitable proxies for palaeoclimatic investigations. In High Asia, the pioneer work of Liang et al. (Liang E, Lu X, Ren P, Li X, Zhu L, Eckstein D, 2012. Annual increments of juniper dwarf shrubs above the tree line on the central Tibetan Plateau: a useful climatic proxy. Annals of Botany109: 721-728) confirmed the suitability of shrub growth-ring chronologies for palaeoclimatic research. This study presents the first sensitivity study of an annually resolved δ18O time series inferred from Wilson juniper (Juniperus pingii var. wilsonii) from the northern shoreline of lake Nam Co (Tibetan Plateau). METHODS: Based on five individual dwarf shrub discs, a statistically reliable δ18O chronology covering the period 1957-2009 was achieved (expressed population signal = 0.80). Spearman's correlation analysis between the δ18O chronology and climate variables from different sources was applied. In a first step, the suitability of various climate data was evaluated. KEY RESULTS: Examinations of climate-proxy relationships revealed significant negative correlations between the δ18O shrub chronology and summer season moisture variability of the previous and current year. In particular, relative humidity of the previous and current vegetation period significantly determined the proxy variability (ρ = -0.48, P < 0.01). Furthermore, the δ18O variability of the developed shrub chronology significantly coincided with a nearby tree-ring δ18O chronology of the same genus (r = 0.62, P < 0.01). CONCLUSIONS: The δ18O shrub chronology reliably recorded humidity variations in the Nam Co region. The chronology was significantly correlated with a nearby moisture-sensitive tree-ring δ18O chronology, indicating a common climate signal in the two chronologies. This climate signal was likely determined by moisture variations of the Asian summer monsoon. Local climate effects were superimposed on the supra-regional climate signature of the monsoon circulation. Opposing δ18O values between the two chronologies were interpreted as plant-physiological differences during isotopic fractionation processes.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Juniperus pingii var. wilsonii; climate–growth relations; dendrochronology; Tibetan Plateau; δ18O coherence shrub/tree

An updated multi-temporal glacier inventory for the Patagonian Andes with changes between the Little Ice Age and 2016 - Meier, Wolfgang; Grießinger, Jussi; Hochreuther, Philipp; Braun, Matthias (Frontiers in Earth Science, 2018)
Keywords: Glacier change; Little Ice Age; Glacier mapping; South America; Remote sensing

A shift in cloud cover over the southeastern Tibetan Plateau since 1600: evidence from regional tree-ring δ18O and its linkages to tropical oceans. - Liu, Xiaohong; Xu, Guobao; Grießinger, Jussi; An, Wenling; Wang, Wenzhi; Zeng, Xioamin; Wu, Guoju; Qin, Dahe (Quaternary Science Reviews, 2014)
We studied the climatic significance and potential forcing of regional tree-ring δ18O across the southeastern Tibetan Plateau from 1600 to 2009. Three normalized tree-ring δ18O time series showed high signal coherence at both low and high frequencies. A 400 years composite tree-ring δ18O chronology in southeastern Tibetan Plateau was established by averaging Z-score method. The composite δ18O chronology showed that climate changed since 1860, causing a shift in the hydroclimatic regime and in the influence of regional atmospheric circulation. Spatial correlation analysis revealed that tree-ring δ18O was significantly negatively correlated with moisture conditions, and especially with cloud cover during wet summers; the strongest correlation was found for the June to August period. Our regional cloud cover reconstruction for June-August period between 26°N and 34°N and between 89°E and 103°E explained 37.6% of the variation from 1953 to 2009. The climate conditions from 1600 to 1860 (the Little Ice Age) were cold and cloudy, but thereafter became sunnier and warmer. Hydroclimatic variations in this region are primarily affected by atmospheric processes in the tropical Indian Ocean and in the East Pacific Ocean, linked to the El Niño-Southern Oscillation (ENSO). The cloud cover over the southeastern Tibetan Plateau is modulated more strongly by sea surface temperatures in the Indian Ocean than over the Pacific Ocean, suggesting low-frequency responses to anomalous ocean warming. The impact of ENSO on regional tree-ring δ18O series was temporally unstable. Our comparisons among different proxies highlight that a tree-ring δ18O network has great potential to reveal common low-frequency climatic signals in monsoon Asia over long time scales.
Keywords: Asian monsoon; ENSO; Hydroclimate; Sea surface temperature; Southeastern Tibetan Plateau; Tree-ring δ18O

A tree-ring–based summer (June–July) minimum temperature reconstruction for the western Kunlun Mountains since AD 1681 - Huang, Ru; Zhu, Haifeng; Liang, Eryuan; Asad, Fayaz; Grießinger, Jussi (Theoretical and Applied Climatology, 2019)
Knowledge of past climatic variability for the Tibetan Plateau (TP), especially the northwestern part of it, is still limited due to the lack of long-term meteorological records. Within this study, we developed a summer (June–July) minimum temperature reconstruction since 1681 based on annual tree-ring width of Schrenk’s spruce (Picea schrenkiana Fisch. et Mey.) from a humid timberline on the western Kunlun Mountains. Our reconstruction passed the statistical calibration and validation tests, and accounted for 37.69% of the variance for the instrumental record during the period 1960–1996. The reconstruction mainly exhibited annual to decadal temperature variability, with cold periods in 1694–1696, 1745–1749, 1823–1824, and 1915–1921, and warm periods in 1755–1760, 1795–1799, and 1894–1896. Spatial correlations and comparisons with the Asia summer temperature reconstructions further verified our temperature reconstruction and its capability to serve as a proxy for large-scale temperature variability on the northwestern TP. Our results clearly indicate the great potential to perform dendrochronological studies on the western Kunlun Mountains.
CRIS-Team Scopus Importer:2019-10-25

A tree ring-based winter temperature reconstruction for the southeastern Tibetan Plateau since 1340 CE - Huang, Ru; Zhu, Haifeng; Liang, Eryuan; Liu, Bo; Shi, Jiangfeng; Zhang, Ruibo; Yuan, Yujiang; Grießinger, Jussi (Climate Dynamics, 2019)
Keywords: Dendroclimatology; Solar activity; Winter temperature; Southeastern Tibetan Plateau; Volcanic eruption

A tree-ring delta O-18 series from southernmost Fuego-Patagonia is recording flavors of the Antarctic Oscillation - Meier, Wolfgang; Aravena, Juan-Carlos; Jana, Ricardo; Braun, Matthias; Hochreuther, Philipp; Soto-Rogel, Pamela; Grießinger, Jussi (Global and Planetary Change, 2020)
A 154 year-long, tree-ring based stable oxygen isotope time series (delta O-18(TRC)) of the evergreen southern beech (Nothofagus betuloides) was established for the southernmost part of Patagonia. The trees grew on the terminal moraine system of the Schiaparelli Glacier (54.4 degrees S) within the windward and hyper-humid zone of the Austral Andes. The annually resolved delta O-18(TRC) record spans the common period 1861-2015 and is based on the analysis of five individually analyzed tree individuals showing a significant mean interseries correlation (r = 0.69). To date, this time series represents the worldwide southernmost chronology of tree-ring delta O-18(TRC). Variations of the delta O-18(TRC) values are significantly correlated with hydroclimatic conditions, as derived from ERA-Interim re-analysis gridded data. Negative relationships between the delta O-18(TRC)-series and relative humidity (r(OctFeb) = -0.62, p < 0.0001) or the amount of precipitation (rJan-Feb = -0.52, p < 0.0001) can be observed for the austral spring and summer seasons. In contrast, a drier environment will increase the delta O-18(TRC) as revealed by a positive influence of evaporation (r(Sep-Feb) = 0.44, p < 0.01), sea level pressure (r(Oct-Feb) = 0.56, p < 0.0001) or maximum temperature (r(Oct-Feb) = 0.43, p < 0.01). Spatial correlation maps indicate a strong supra-regional influence of climate variables on the chronology. The annular pressure seesaw, termed as Antarctic Oscillation (AAO), mostly influences climate variability within the Southern Hemisphere and is positively correlated with the delta O-18(TRC)-chronology (r(JF) = 0.61, p < 0.0001). Since our chronology, as well as a neighboring delta O-18(TRC) chronology from the Perito Moreno Glacier (50 degrees S), are showing a high correspondence in their sensitivities to climate variabilities and towards the AAO, we merged both time series into a mean chronology. This new regional mean delta O-18(TRC)-chronology is highly sensitive to variations of the AAO (r = 0.79, p < 0.0001)) and is tested for the suitability to reconstruct the AAO for the last 150 years. The reconstructed time series of the AAO reveals an increasing trend towards more positive index values, which is associated with an amplification in the amount of precipitation and wind speed in southernmost South America.
CRIS-Team WoS Importer:2020-12-11

Climate Change and New Markets: Multi-Factorial Drivers of Recent Land-Use Change in The Semi-Arid Trans-Himalaya, Nepal - Meier, Wolfgang; Pohle, Perdita; Grießinger, Jussi (Land, 2022)
The Nepalese Mustang District is subject to profound environmental change. In recent decades, rising temperatures have been apparent, accompanied by increasing precipitation variability and a reduction in glacier extent. In a semi-arid climate, this reduces water availability and threatens irrigation-based subsidence agriculture. In addition, the region is experiencing rapid socio-economic change due to a new road connecting the former periphery to new markets downstream. This enables a higher market orientation for agricultural products and improved accessibility for tourists. In recent decades, these changes have triggered severe transformations in the local land-use systems and settlements, which are investigated in this study. Detailed on-site re-mappings of the settlements of Marpha and Kagbeni were performed based on historical maps from the early 1990s. Additionally, land-use patterns and functionality of buildings in the district capital of Jomsom and in the settlement Ranipauwa/Muktinath were mapped. For all settlements, a profound increase in cash crop (apple) cultivation can be observed since the 1990s. Recently, new cultivation practices such as intercropping have been extensively introduced as an adaptation strategy to climate extremes. Demand for different crops from the new markets downstream is causing a significant decline in local, well-established cultivation of traditional crops such as buckwheat. This corroborates with an increasing demand for freshwater for the enhanced vegetable cultivation used for inter-cropping. Simultaneously, the freshwater demands from the tourism sector are steadily increasing. In a region where water quality is deteriorating and springs are already drying up due to climate change, this will probably lead to further challenges regarding the allocation of water in the future.
CRIS-Team WoS Importer:2022-10-07

Contribution of winter precipitation to tree growth persists until the late growing season in the Karakoram of northern Pakistan - Huang, Ru; Zhu, Haifeng; Liang, Eryuan; Bräuning, Achim; Zhong, Linhao; Xu, Chenxi; Feng, Xiaoyu; Asad, Fayaz; Sigdel, Shalik Ram; Li, Lingcheng; Grießinger, Jussi (Journal of Hydrology, 2022)
Identifying the influence of seasonal source water on tree growth is essential to understand the effect of climate change on forest dynamics. However, due to the lack of available long-term monitoring studies, little is known on how long moisture originating from winter precipitation influences tree growth in the following growing season. Herein, we developed a tree-ring latewood oxygen isotope (δ18OLW) chronology from the Karakoram (1955–2013) in northern Pakistan. We investigated whether winter climate signals are incorporated in the δ18OLW and how long winter precipitation through soil moisture contributed to tree growth during the growing season. Significant correlations were found between δ18OLW with both, winter to spring (January–May) temperature (r = 0.43, p < 0.05) and summer (July–August) precipitation (Local: r = −0.38, p < 0.05; Moisture source region: r = −0.44, p < 0.05). As shown by the cross-spectrum and commonality analysis, the climate signals in the δ18OLW are frequency-dependent. Winter temperature signals stored in the δ18OLW variations dominate at low frequencies more than 7 years (59% variance explained), while the summer precipitation signals dominate variations with higher frequencies shorter than 7 years (47% variance explained). Further analysis using reanalysis data shows that the growing season soil moisture at root depth (10–40 cm) is more strongly related to winter precipitation than to summer rainfall. Winter precipitation formed as ground snow provides root-zone soil moisture and tree growth via snowmelt during the growing season. Our study highlights that winter precipitation is the dominant water source contributing to Karakoram tree growth until the late growing season. Given the possibility of a decrease in winter precipitation under climate change in the Karakoram region, local forest is potentially threatened by the declining water supply during the growing season.
CRIS-Team Scopus Importer:2022-02-11
Keywords: Frequency dependence; Karakoram; Source water; Stable oxygen isotope; Tree ring latewood

“dendRoAnalyst”: A tool for processing and analysing dendrometer data - Aryal, Sugam; Häusser, Martin; Grießinger, Jussi; Fan, Zexin; Bräuning, Achim (Dendrochronologia, 2020)
Dendrometers are vital tools for studying the response of trees to intra-annual environmental changes in different temporal resolutions, ranging from hourly, daily to weekly time resolution. Dendrometers are increasingly used in forest management and tree physiological studies. Besides the data analysis, data processing is also challenging, time-consuming and potentially error-prone due to the immense number of measurements generated by self-registering electronic dendrometers. We present the package ‘dendRoAnalyst’ based on R statistical software to process and analyse dendrometer data using various approaches. This package offers algorithms for handling and pre-cleaning of dendrometer data before the application of subsequent data analytical steps. This includes identifying and erasing artefacts in dendrometer datasets not related to actual stem circumference change, identifying data gaps within records, and the possibility of change(s) in temporal resolution. Furthermore, the package can calculate different daily statistics of dendrometer data, including the daily amplitude of tree growth. The package dendRoAnalyst is therefore intended to facilitate researchers with a collection of functions for handling and analysing dendrometer data.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Dendrometer; R-package; Stem-cycle approach; Stem-variation analysis; Tree-growth monitoring; Zero-growth approach

Dendroecological Perspectives on Climate Change on the Southern Tibetan Plateau - Bräuning, Achim; Grießinger, Jussi; Hochreuther, Philipp; Wernicke, Jakob (Climate Change, Glacier Response, and Vegetation Dynamics in the Himalaya. Contributions Toward Future Earth Initiatives., 2016)
Tree rings are indicators of historic environmental changes and plant response to past and current climate change. Summer temperature reconstructions from maximum latewood density on the southeastern Tibetan plateau (TP) for the past 600 years revealed cool summer temperatures between ca. 1580 and 1790 A.D., corresponding to the “Little Ice Age (LIA).” This period was characterized by several glacier advance periods, with a maximum glacier extent ending around 1740–1780 A.D. and smaller readvance phases during the early nineteenth to late nineteenth century. Stable carbon isotope analyses of tree-ring cellulose indicate species-specific ecophysiological response patterns of trees to environmental conditions related to enhanced atmospheric CO2 levels and drier site conditions which might affect future forest composition. Spatial patterns of altitudinal changes of climate-growth relationships indicate the dominance of different growth-limiting factors in different regions of the TP. In semiarid regions along the western distribution limit of forests, moisture availability during the growing season is most relevant for growth of juniper tree species even in high altitudes. In contrast, warmer temperatures have a stimulating effect on radial growth close to the upper tree limit on the humid eastern TP. These findings are corroborated by first studies of cambial phenology, indicating a stimulating influence of early growing season temperatures on cell formation. In the dry northeastern TP, wet conditions during the main growing season in June are favorable for radial growth. Due to the low number of studies and a long history of human impact on forests, a climate-driven upward shift of the upper tree limit cannot yet clearly be stated. Tree-ring analyses on long-living dwarf shrubs may increase the potential for dendrochronological climate reconstructions beyond the upper limit of tree growth on the TP.
Keywords: Tibetan plateau; Climate reconstruction; Tree rings; Stable isotopes; Dendroecology; Glacier history

Development of dendrochronology and its track in China since 1990 reflected by bibliometric analysis - Feng, Xiaoyu; Zhu, Haifeng; Liang, Eryuan; Grießinger, Jussi; Zhu, Xiaolong; Bräuning, Achim (Dendrochronologia, 2024)
Dendrochronology is a discipline that uses tree rings to study the history and dynamics of the earth system, such as climate change, natural disasters, and human activities. This study aims to evaluate the development of dendrochronology and its track in China from 1990 to 2022 using a bibliometric analysis approach. We screened the Web of Science Core Collection for documents related to dendrochronology and analyzed them according to indicators related to production, cooperation, citation, and keywords. Our study revealed that the number of dendrochronological publications increased continuously, reaching more than 800 in 2021, with the USA and China being the top two countries. The cooperation network of dendrochronology was mainly centered between North America and Europe, with China having a moderate level of collaboration with other countries and regions like the USA and Canada. Comprehensive research has been conducted within diverse fields of dendrochronology in the world and in China, but dendrochronological research focusing on forestry and climatology represented a slightly higher proportion of research originating from China. The integration of dendrochronology with other disciplines and techniques, such as remote sensing, artificial intelligence, and modeling, may be hotspots in future research, as indicated by the increasing co-occurrence analysis of keywords in the most recent years. This study suggests that Chinese Dendrochronology still requires improved international collaboration, diversified research topics beyond climate reconstructions, and more emphasis on tree-ring methods to advance this discipline globally, despite of increasing rank of publications in the past decade.
CRIS-Team Scopus Importer:2024-04-26
Keywords: Bibliometric analysis; Dendrochronology; Research development; Web of Science

Does increasing intrinsic water use efficiency (iWUE) stimulate tree growth at natural alpine timberline on the southeastern Tibetan Plateau? - Huang, Ru; Zhu, Haifeng; Liang, Eryuan; Liu, Xiaohong; Grießinger, Jussi; Wu, Guoju; Li, Xiaoxia; Bräuning, Achim (Global and Planetary Change, 2017)
Little is known about whether increasing iWUE (intrinsic water use efficiency) can stimulate tree growth in the temperature-limited natural timberlines. Here, we presented the basal area increment (BAI) and iWUE chronologies of Smith fir (Abies georgei var. smithii) from 1900 to 2006 at a high-elevation (ca. 4400 m a.s.l.) timberline in the humid Sygera Mountains, southeastern Tibetan Plateau (TP). The commonality analysis model was applied to investigate the relationships among BAI, temperatures, atmospheric CO2 concentration (Ca) and iWUE during 1961–2006, taking into account of both pure and joint effects. As illustrated by the commonality analysis model, the pure effect of Ca (39.15%) had more stronger influence on iWUE than that of the Tmean (annul mean temperature, 0.12%), but the joint effect between Ca and Tmean (49.79%) on iWUE was stronger than any pure effect for the raw data with an increasing trend. For the first-difference data with year-to-year variations, the pure effect of Ca (7.72%) on iWUE was stronger than that of Tmean (0.59%) and the joint effect between them (0.59%). All above imply the Ca is the dominant factor for iWUE both for the 46-year trend and interannual variations. In addition, as showed by the commonality analysis model, the pure effect of iWUE (17.57%) played a much more important role on BAI than that of temperatures (smt, mean temperature during June, July, August of current year, 5.92%; amt, mean temperature during September, October, November of previous year, 3.04%), while joint effects of iWUE and temperatures contributed more (27.96%; 13.90%; 16.47%) to the BAI than their pure effects for the raw data with an increasing linear trend. For the first-difference data with interannual variations, the pure effect of smt (12.45%) had much more effect on BAI than that of iWUE (5.49%), at the same time the joint iWUE and temperatures contributed less (3.56%; 1.9%; 1.31%) to the BAI than their pure effects. These results suggest that an increasing iWUE could enhance 46-year increasing tree growth trend at humid and high-elevation timberlines, supporting the CO2 fertilization hypothesis, while temperatures dominate the interannual variations of tree growth.
Keywords: Upper timberline; Tree growth; Intrinsic water use efficiency; CO2 fertilization; Climate warming; Southeastern Tibetan Plateau

Drought signals in tree-ring stable oxygen isotope series of Qilian juniper from the arid northeastern Tibetan Plateau - Qin, Chun; Yang, Bao; Bräuning, Achim; Grießinger, Jussi; Wernicke, Jakob (Global and Planetary Change, 2015)
For the mechanistic understanding of hydroclimate variability, stable oxygen isotopic ratios (δO) of tree-ring α-cellulose can play a key role in paleoclimatic research. On the north-east Tibetan Plateau (TP), a region particularly sensitive to climate change, there exists a distinct lack of δO research in tree-ring archives. The few currently existing tree-ring δO chronologies were obtained by pooling the wood material from the same year from different trees prior to preparation and analysis. Although this method is time and cost efficient, it might impede the analysis of changes within the internal variability of oxygen isotope signals and a deeper understanding of the resulting climate reconstruction. We selected five Qilian juniper (Sabina przewalskii Kom.) trees covering the period 1951-2011 on the north-east TP to investigate the climate signals contained in stable oxygen isotopic composition records obtained using single tree analysis. Although the inter-series correlation between the five individual δO series indicates a highly significant relationship (mean r=0.59, n=59, p=0.01), the five individual δO series show significantly differently mean values. We found significant negative correlations between drought/hydroclimatically triggered climate parameters (PDSI, precipitation) and each of the individual δO series. Spatial correlation maps indicate negative correlation of tree-ring δO and Indian Ocean sea surface temperatures, and inverse correlation patters of moisture conditions on the northern and southern TP. Our results provide a reference for future research on stable oxygen isotope/climate signals in the species S. przewalskii Kom.
Keywords: Hydroclimate; North-east Tibetan plateau; Sabina przewalskii; Stable oxygen isotopes; Wood cellulose

Drought, temperature, and moisture availability: understanding the drivers of isotopic decoupling in native pine species of the Nepalese Himalaya - Aryal, Sugam; Grießinger, Jussi; Gaire, Narayan Prasad; Bhattarai, Tribikram; Bräuning, Achim (International Journal of Biometeorology, 2024)
The Himalayas experienced long-term climate changes and recent extreme weather events that affected plant growth and the physiology of tree species at high-elevation sites. This study presents the first statistically robust δ18OTR chronologies for two native pine species, Pinus roxburghii, and Pinus wallichiana, in the lower Nepalese Himalaya. The isotope chronologies exhibited 0.88‰ differences in overall mean isotope values attributed to varying elevations (460–2000 m asl). Comparative analysis of climate response using data sets from different sources and resolutions revealed the superiority of the APHRODITE (Asian Precipitation – Highly-Resolved Observational Data Integration Towards Evaluation) data set calibrated for the South Asian Summer Monsoon (SASM)-dominated region. Both species exhibited negative correlations with monsoon precipitation and positive correlations with temperature. However, during the peak monsoon season (July-August), daily resolved climate data disentangled statistically insignificant relationships, and revealed that δ18OTR is influenced by atmospheric moisture. Both congeneric species showed a decoupling between the chronologies after 1995. However, no significant change in air moisture origin and monsoon regime between the study sites was observed, indicating a consistent dominant moisture source during different monsoon seasons. Besides, we also observed the decreased inter-series correlation of both δ18OTR chronologies after 1995, with P. wallichiana experiencing a steeper decrease than P. roxburghii. The weakening correlations between and within the chronologies coincided with a regional drought during 1993–1995 in both sites, highlighting the strong regulation of local climate on the impact of regional extreme climate events. Our findings emphasise the importance of employing climate data with optimal spatial and temporal resolution for improved δ18OTR-climate relationships at the intra-annual scale while considering the influence of site-specific local environmental conditions. Assessing climate data sets with station data is vital for accurately interpreting climate change’s impact on forest response and long-term climate reconstructions.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Isotopic decoupling; Local environmental effects; Native pine species; Nepalese Himalaya; Precipitation; Stable oxygen isotopes; Temperature

Editorial: Climate Impacts on Glaciers and Biosphere in Fuego-Patagonia - Schneider, Christoph; Braun, Matthias; Schaefer, Marius; Grießinger, Jussi; Casassa, Gino (Frontiers in Earth Science, 2020)
CRIS-Team Scopus Importer:2020-05-05
Keywords: biosphere; climate change; climate variability; cryosphere; Patagonia; Tierra del Fuego

Enhanced Variability and Declining Trend of Soil Moisture Since the 1880s on the Southeastern Tibetan Plateau - Wang, Lu; Liu, Hongyan; Grießinger, Jussi; Chen, Deliang; Sun, Changfeng; Fang, Congxi (Water Resources Research, 2023)
Historical soil moisture (SM) variations, trends, and their driving factors remain scarce for the area of Tibetan Plateau (TP), which hinders putting a sensible assessment of the current and future ecological drought risk into perspective. Here, we report the first three century-long regional summer (July-August) SM reconstruction for the southeastern TP during 1691-2007 CE using a paleoclimate proxy, that is, tree-ring delta O-18. The SM reconstruction, which explained 60.9% of the actual variance, revealed that an abrupt wet-to-dry change occurred in 1884. After 1884, SM exhibited a decreasing trend and enhanced variability, and dry summers occurred more frequently. In particular, the variability in SM reached an unprecedented level after the 1950s relative to that during the past three centuries. A structural equation model and running correlation analysis revealed that SM variation was mainly controlled by precipitation rather than temperature. This indicates that the anthropogenic-related weakening of the Indian summer monsoon played a more dominant role in SM changes after 1884 than the increase in temperature. If the SM variability is to be further increased in the future, it may undermine ecosystem stability and forest health. The results of this study are significant for predicting ecological drought in ecologically vulnerable regions such as the High Asia.
CRIS-Team WoS Importer:2023-04-07

Erratum to: Tree rings reveal globally coherent signature of cosmogenic radiocarbon events in 774 and 993 CE (Nature Communications, (2018), 9, 1, (3605), 10.1038/s41467-018-06036-0) - Buntgen, Ulf; Wacker, Lukas; Galvan, J. Diego; Arnold, Stephanie; Arseneault, Dominique; Baillie, Michael; Beer, Jurg; Bernabei, Mauro; Bleicher, Niels; Boswijk, Gretel; Bräuning, Achim; Carrer, Marco; et al. (Nature Communications, 2018)

Evaluation of Different Pooling Methods to Establish a Multi-Century delta O-18 Chronology for Paleoclimate Reconstruction - Foroozan, Zeynab; Grießinger, Jussi; Pourtahmasi, Kambiz; Bräuning, Achim (Geosciences, 2019)
To develop multi-century stable isotope chronologies from tree rings, pooling techniques are applied to reduce laboratory costs and time. However, pooling of wood samples from different trees may have adverse effects on the signal amplitude in the final isotope chronology. We tested different pooling approaches to identify the method that is most cost-efficient, without compromising the ability of the final chronology to reflect long-term climate variability as well as climatic extreme years. As test material, we used delta O-18 data from juniper trees (Juniperus polycarpus) from Northern Iran. We compared inter-tree and shifted 5-year blocks serial pooling of stable isotope series from 5 individual trees and addition of one single series to a shifted serial pooled chronology. The inter-tree pooled chronology showed the strongest climate sensitivity and most synchronous delta O-18 variations with the individual tree ring analyses, while the shifted block chronologies showed a marked decline in high-frequency signals and no correlations with climate variables of the growth year. Combinations of block-pooled and single isotope series compensated the high-frequency decline but added tree-individual climatic signals. Therefore, we recommend pooling calendar synchronous tree rings from individual trees as a viable alternative to individual-tree isotope measurements for robust paleoclimate reconstructions.
CRIS-Team WoS Importer:2019-07-19

Großräumige morphologische Entwicklung im Umfeld der ostfriesischen Insel Wangerooge - Konsequenzen für zukünftige Inselschutzkonzepte. Eine GIS - gestützte Analyse. - Grießinger, Jussi (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2002)
UnivIS-Import:2016-07-26:Pub.2002.nat.dgeo.IG.zentr.grorum

High-elevation shrub-ring δ18O on the northern slope of the central Himalayas records summer (May–July) temperatures - Huang, Ru; Zhu, Haifeng; Liang, Eryuan; Grießinger, Jussi; Dawadi, Binod; Bräuning, Achim (Palaeogeography, Palaeoclimatology, Palaeoecology, 2019)
Keywords: Central Himalayas; Shrub-ring oxygen isotope; Southern Tibetan Plateau; Climatic proxy; Paleoclimatology

Himalayan fir reveals moist phase during Little Ice Age in the Kashmir region of the western Himalayas - Chinthala, Bency David; Ranhotra, Parminder Singh; Grießinger, Jussi; Singh, Chandra Prakash; Bräuning, Achim (Quaternary Science Reviews, 2023)
The Kashmir region in the western Himalayas is located in a transition zone between areas dominated by the South Asian Summer Monsoon (SASM) and the North Atlantic Oscillation (NAO). Currently being primarily influenced by westerly disturbances (WDs), the area is important to decipher teleconnections between these two important circulation systems for the assessment of past climate variability. We evaluated climate-growth relationships of Abies pindrow (Royle ex D. Don) and reconstructed April to June (AMJ) self-calibrated Palmer drought severity index (scPDSI) for the south Kashmir region during the period 1643–2016 CE. Our reconstructed scPDSI revealed a long wet phase during 1650–1816 CE, indicating the impact of the Little Ice Age (LIA) over the region, followed by prominent drier post-LIA episodes. The mid 18th century (1730–1760 CE) was the wettest period in the past four centuries, whereas the period 1817 to 1865 CE marked the driest phase. These phases are consistent with other precipitation reconstructions from the WD-dominated western and Trans-Himalayan regions, but inconsistant with summer precipitation reconstructions from the SASM-dominated Himalayan regions. A significant positive correlation between our scPDSI reconstruction and the North Atlantic Oscillation (NAO) for the wet phase of the LIA suggests that the NAO remained dominant in modulating the winter and spring precipitation at the study region. During the 19th and 20th centuries, scPDSI was either weakly or negatively correlated with the NAO index, indicating the influence of other atmospheric circulation systems in driving the spring/summer precipitation in the study area. This study, augmented with other moisture records, contributes to analyze the temporal and spatial extent of moisture variability in a regional perspective.
CRIS-Team Scopus Importer:2023-06-23
Keywords: Abies pindrow; Climate indices; North Atlantic oscillation; Palmer drought severity index; Tree-ring width; Volcanic eruption; Westerly disturbances

Hydroclimatic variability of the Tibetan Plateau during the past millennium - Wernicke, Jakob; Hochreuther, Philipp; Grießinger, Jussi; Zhu, Haifeng; Wang, Lili; Bräuning, Achim (TRACE - Tree Rings in Archaeology, Climatology and Ecology, Vol. 13: Proceedings of the DENDROSYMPOSIUM 2014 Scientific Technical Report 15/06, GFZ Potsdam, 2015)

Impact of extreme weather events on aboveground net primary productivity and sheep production in the magellan region, southernmost chilean patagonia - Soto-Rogel, Pamela; Aravena, Juan Carlos; Meier, Wolfgang; Gross, Pamela; Pérez, Claudio; González-Reyes, Álvaro; Grießinger, Jussi (Geosciences, 2020)
Spatio-temporal patterns of climatic variability have effects on the environmental conditions of a given land territory and consequently determine the evolution of its productive activities. One of the most direct ways to evaluate this relationship is to measure the condition of the vegetation cover and land-use information. In southernmost South America there is a limited number of long-term studies on these matters, an incomplete network of weather stations and almost no database on ecosystems productivity. In the present work, we characterized the climate variability of the Magellan Region, southernmost Chilean Patagonia, for the last 34 years, studying key variables associated with one of its main economic sectors, sheep production, and evaluating the effect of extreme weather events on ecosystem productivity and sheep production. Our results show a marked multi-decadal character of the climatic variables, with a trend to more arid conditions for the last 8 years, together with an increase in the frequency of extreme weather events. Significant percentages of aboveground net primary productivity (ANPP) variance is explained by high precipitation, mesic temperatures, and low evapotranspiration. These conditions are, however, spatially distributed in the transition zone between deciduous forests and steppe and do not represent a general pattern for the entire region. Strong precipitation and wind velocity negatively affect lamb survival, while temperature and ANPP are positively correlated. The impact of extreme weather events on ANP and sheep production (SP) was in most of the cases significantly negative, with the exception of maximum temperature that correlated with an increase of ANPP, and droughts that showed a non-significant negative trend in ANPP. The examination of these relationships is urgent under the current scenario of climate change with the acceleration of the environmental trends here detected.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Aboveground net primary productivity; Climate variability; Extreme weather events; Magellan region; Patagonia; Sheep production

Imprints of climate signals in a 204 year δ18O tree-ring record of nothofagus pumilio from Perito Moreno Glacier, Southern Patagonia (50◦S) - Grießinger, Jussi; Langhamer, Lukas; Schneider, Christoph; Saß, Björn; Steger, David; Skvarca, Pedro; Braun, Matthias; Meier, Wolfgang; Srur, Ana M.; Hochreuther, Philipp (Frontiers in Earth Science, 2018)
A 204 year-long record of delta O-18 in tree-ring cellulose of southern beech (Nothofagus pumilio) from a site near Perito Moreno Glacier (50:S) in Southern Patagonia was established to assess its potential for a climate reconstruction. The annually resolved oxygen isotope chronology is built out of seven individual tree-ring delta O-18 series with a significant mean inter-series correlation (r = 0.61) and is the first of its kind located in Southern America south of 50 degrees S. Over a common period from 1960 to 2013 of available stationary and high-resolution gridded CRU TS v. 4.01 data, the delta O-18 chronology exhibits a strong sensitivity toward hydroclimatic as well as temperature parameters as revealed by correlation analyses. Among these, positive correlations with maximum temperature in the first part of the summer season (CRU r(ONDJ) = 0.51, p < 0.01) and negative correlations with precipitation in the latter half of the vegetation period (CRU r(ONDJ) = -0.54, p < 0.01) show the highest sensitivities. A strong supra-regional influence of the Southern Annular Mode (SAM) is clearly recorded in this chronology as indicated by significant positive correlations during the vegetation period (r(ONDJ) = 0.62, p < 0.01). This indicates that the presented delta O-18-chronology shows great promise to reconstruct the influence and variability of the SAM within the last two centuries in southern South America. The modulation of positive and negative anomalies within this series can be interlinked to changes in moisture source origin as revealed by backward trajectory modeling. Additionally, these anomalies can be directly associated to positive or negative phases of the Antarctic Oscillation Index (AAOI) and therefore the strength of the Westerlies. Aligned by the analysis on the influence of different main weather types on the delta O-18 chronology it is shown that such time-series hold the potential to additionally capture their respective influence and change during the last centuries.
Keywords: Backward trajectory modeling; Perito Moreno Glacier; Southern Annular Mode (SAM); Main weather types; Nothofagus pumilio; Southern Patagonia; Tree-ring δ18O

Influence of the Indian Ocean Dipole on tree-ring δ18O of monsoonal Southeast Tibet - Hochreuther, Philipp; Wernicke, Jakob; Grießinger, Jussi; Mölg, Thomas; Zhu, Haifeng; Wang, Lily; Bräuning, Achim (Climatic Change, 2016)
We present a newly developed, annually resolved tree-ring cellulose δO chronology for the southeastern Tibetan Plateau (TP) from Sikkim larch (Larix griffithii), spanning between 1684 and 2012. Comparisons with local and regional climate data reveal strong positive correlations with monthly sunshine hours, temperature and daily temperature amplitude as well as strong negative correlations with relative humidity, vapor pressure, rain days per month and cloud cover of August. Relationships with local and regional tree-ring δO chronologies are stable and highly significant. Over the 20th century, we find no long-term climatic trends. This is consistent with other tree-ring δO chronologies of other tree species south of the Himalayas, but contrasts with results from isotope studies north of the Himalayas. This suggests stable macroclimatic flow patterns throughout the last centuries for the southern tree stands. In terms of large-scale climate dynamics, we find evidence of a significant 30-year wave influencing our tree-ring oxygen chronology, most probably induced by the Indian Ocean Dipole and influencing tree-ring oxygen isotope chronologies along the southeastern Himalaya and the southeastern rim of the TP. This pattern is spatially and temporarily consistent among the chronologies and has apparently strengthened during the last century. During periods of strong positive dipole mode activity, the dipole mode index shows positive correlations with the δO of tree-rings on the southeastern TP.

Insect infestations have an impact on the quality of climate reconstructions using Larix ring-width chronologies from the Tibetan plateau - Aryal, Sugam; Grießinger, Jussi; Arsalani, Mohsen; Meier, Wolfgang; Fu, Pei Li; Fan, Ze Xin; Bräuning, Achim (Ecological Indicators, 2023)
Insect outbreaks are proven to harm trees, reducing their biomass accumulation due to the defoliation of leaves during the growing season. Various defoliators are responsible for the formation of extremely narrow tree rings in different tree species. In climate reconstructions based on tree-ring width, such narrow rings are often considered as noise, because their formation is not entirely caused by climatic conditions. Thus, the impact of defoliators should be removed (nullified) for unbiased climate reconstructions. This study mainly describes a statistical approach to disentangle the effects of Larch budmoth(LBM) (Zeiraphera diniana) and climate for an unbiased temperature reconstruction in the Bai-Ma mountain area in Southwest China using Larix potaninii. After applying our new approach, growth-climate relationships improved significantly (p < 0.05), especially with minimum temperature during the growing season (June-September). The resulting temperature reconstruction (BTmin) covers the period 1712–2020 CE (313 years). Our final temperature reconstruction for the Bai-Ma area showed a wiggly trend from 1712 to 1980, with some cool periods (1791–1853 and 1888–1930) and warm episodes (1724–1745, 1854–1887, 1950–1967). During the recent 50 years, BTmin reveal an alarming warming trend of up to 0.4 °C per decade. We also observed a strong coherency of BTmin with regional temperature series. Furthermore, we detected a differential effect of various climate modes, with the most substantial impact of the Atlantic Multidecadal Oscillation (AMO) on BTmin (p < 0.01). Interestingly, the Pacific Decadal Oscillation (PDO) showed a coupled effect along with AMO on BTmin. As revealed in this study, removing the LBM effect improved the chronology's climate sensitivity, leading to a more robust transfer function and in terms of insect infestations unbiased climate reconstructions. Thus, it is recommended to check ring-width data for any periodicity potentially related to insect outbreaks and correct the original data before using tree-ring chronologies for climate reconstruction.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Defoliator; Dendrochronology; Larch budmoth; Minimum temperature; Outbreak; Yunnan

Integrative Hochgebirgsökologie in der Hochschullehre – “Umweltwandel in den Südalpen” - Peters, Thorsten; Bäumler, Rupert; Bräuning, Achim; Grießinger, Jussi; Richter, Michael (Arbeitskreis Hochgebirge, 2013)

Inter-tree correlation and climatic response of tree-ring δ18O in Chinese fir: Implications for cross-dating and climatic reconstruction in Central East China - Zhao, Yesi; Yang, Bao; Zhang, Peng; Luo, Jiayan; Grießinger, Jussi; Zhang, Hongyan; Liang, Chenghong; Ma, Zaiqin; Gu, Hongliang; Zhang, Yizhong (Dendrochronologia, 2023)
The availability of both ancient and modern wood samples enables the Chinese fir (Cunninghamia lanceolata) in Central East China to become a potential tree species for dendroclimatic reconstruction over the Common Era. However, the potential of using tree-ring α-cellulose oxygen isotope ratios (δ18OTRC) in Chinese fir for the purposes of cross-dating and climatic reconstruction remains unexplored. Here we presented three δ18OTRC chronologies (1954–2006 CE) for the whole-ring (δ18OWR), earlywood (δ18OEW), and latewood (δ18OLW) in Chinese fir. The results indicated that the δ18OWR had the highest correlation among individual trees. Using the δ18OWR instead of the conventionally employed TRW can facilitate the cross-dating procedure. The δ18OWR, δ18OEW, and δ18OLW exhibited the strongest relationships with the hydroclimate variables during the entire (June–September), early (June–July), and late (August–September) summer, respectively. The climate conditions preceding the growing season had a stronger influence on δ18OEW than δ18OLW. Using the δ18OWR and δ18OEW to reconstruct the hydroclimate variations may result in greater bias than the use of δ18OLW. Our study demonstrated that the δ18OTRC in Chinese fir from Central East China has the potential for cross-dating and summer hydroclimate reconstruction.
CRIS-Team Scopus Importer:2023-10-27
Keywords: Central East China; Chinese fir; Climatic reconstruction; Cross-dating; Tree-ring oxygen isotope ratios

Intra-annual radial growth of Pinus kesiya var. langbianensis is mainly controlled by moisture availability in the Ailao Mountains, southwestern China - Fan, Ze Xin; Bräuning, Achim; Fu, Pei Li; Yang, Rao Qiong; Qi, Jin Hua; Grießinger, Jussi; Gebrekirstos, Aster (Forests, 2019)
Intra-annual monitoring of tree growth dynamics is increasingly applied to disentangle growth-change relationships with local climate conditions. However, such studies are still very limited in subtropical regions which show a wide variety of climate regimes. We monitored stem radius variations (SRV) of Pinus kesiya var. langbianensis (Szemao pine) over five years (2012-2015 and 2017) in the subtropical monsoon mountain climate of the Ailao Mountains, Yunnan Province, southwest China. On average, the stem radial growth of Szemao pine started in early March and ended in early October, and the highest growth rates occurred during May to June. Stem radius increments were synchronous with precipitation events, while tree water deficit corresponded to the drought periods. Correlation analysis and linear mixed-effects models revealed that precipitation and relative humidity are the most important limiting factors of stem radial increments, whereas air temperature and vapor pressure deficit significantly affected tree water balance and may play an important role in determining the growing season length and seasonality (i.e., duration, start, and cessation). This study reveals that moisture availability plays a major role for tree growth of P. kesiya var langbianensis in the Ailao Mountains, southwest China.
CRIS-Team Scopus Importer:2019-10-25
Keywords: Ailao Mountains; Climate response; Pine; Point dendrometer; Stem radius variations; Tree water deficit

INTRAGRO: A machine learning approach to predict future growth of trees under climate change - Aryal, Sugam; Grießinger, Jussi; Dyola, Nita; Gaire, Narayan Prasad; Bhattarai, Tribikram; Bräuning, Achim (Ecology and Evolution, 2023)
The escalating impact of climate change on global terrestrial ecosystems demands a robust prediction of the trees' growth patterns and physiological adaptation for sustainable forestry and successful conservation efforts. Understanding these dynamics at an intra-annual resolution can offer deeper insights into tree responses under various future climate scenarios. However, the existing approaches to infer cambial or leaf phenological change are mainly focused on certain climatic zones (such as higher latitudes) or species with foliage discolouration during the fall season. In this study, we demonstrated a novel approach (INTRAGRO) to combine intra-annual circumference records generated by dendrometers coupled to the output of climate models to predict future tree growth at intra-annual resolution using a series of supervised and unsupervised machine learning algorithms. INTRAGRO performed well using our dataset, that is dendrometer data of P. roxburghii Sarg. from the subtropical mid-elevation belt of Nepal, with robust test statistics. Our growth prediction shows enhanced tree growth at our study site for the middle and end of the 21st century. This result is remarkable since the predicted growing season by INTRAGRO is expected to shorten due to changes in seasonal precipitation. INTRAGRO's key advantage is the opportunity to analyse changes in trees' intra-annual growth dynamics on a global scale, regardless of the investigated tree species, regional climate and geographical conditions. Such information is important to assess tree species' growth performance and physiological adaptation to growing season change under different climate scenarios.
CRIS-Team Scopus Importer:2023-11-03
Keywords: dendrometer; growing-season change; intra-annual growth; machine learning algorithm; Pinus roxburghii; sub-tropical Nepal

Isotope studies along a high-elevation transect on the Tibetan Plateau - Grießinger, Jussi; Bräuning, Achim; Schleser, Gerhard Hans (TRACE - Tree Rings in Archaeology, Climatology and Ecology, Vol. 3: Proceedings of the DENDROSYMPOSIUM 2004 Schriften des Forschungszentrums Jülich, Reihe Umwelt, Vol. 53, 2005)
UnivIS-Import:2015-03-09:Pub.2005.nat.dgeo.IG.LGIPDT.isotop

Late Holocene Asian summer monsoon variability reflected by δ18O in tree-rings from Tibetan junipers - Grießinger, Jussi; Bräuning, Achim; Helle, Gerhard; Thomas, Axel; Schleser, Gerhard Hans (Geophysical Research Letters, 2011)
Recent warming in High Asia might have a strong impact on Asian summer monsoon variability with consequences for the hydrological cycle. Based on correlations between climate data, the tree-ring delta O-18 of high-elevation junipers is an indicator of August precipitation. Thus, our 800-year long annually resolved oxygen isotope series reflects long-term variations in summer monsoon activity on the southern Tibetan plateau. Summer precipitation was reduced during 13th-15th centuries and since the 19th century, whereas the Little Ice Age period (15th-19th century) was rather moist. The late 20th century was among the driest periods during the past 800 years, showing a tendency to slightly wetter conditions after AD 1990. Citation: Griessinger, J., A. Brauning, G. Helle, A. Thomas, and G. Schleser (2011), Late Holocene Asian summer monsoon variability reflected by delta O-18 in tree-rings from Tibetan junipers, Geophys. Res. Lett., 38, L03701, doi:10.1029/2010GL045988.
UnivIS-Import:2015-04-20:Pub.2011.nat.dgeo.IG.LGIPDT.lateho

Late Holocene Glacial Fluctuations of Schiaparelli Glacier at Monte Sarmiento Massif, Tierra del Fuego (54 degrees 24 ' S) - Meier, Wolfgang; Aravena, Juan-Carlos; Grießinger, Jussi; Hochreuther, Philipp; Soto-Rogel, Pamela; Zhu, Haifeng; De Pol-Holz, Ricardo; Schneider, Christoph; Braun, Matthias (Geosciences, 2019)
The Magallanes-Tierra del Fuego region, Southern Patagonia (53-56 degrees S) features a plethora of fjords and remote and isolated islands, and hosts several thousand glaciers. The number of investigated glaciers with respect to the multiple Neoglacial advances is based on a few individual studies and is still fragmentary, which complicates the interpretation of the glacial dynamics in the southernmost part of America. Schiaparelli Glacier (54 degrees 24 ' S, 70 degrees 50 ' W), located at the western side of the Cordillera Darwin, was selected for tree-ring-based and radiocarbon dating of the glacial deposits. One focus of the study was to address to the potential dating uncertainties that arise by the use of Nothofagus spp. as a pioneer species. A robust analysis of the age-height relationship, missing the pith of the tree (pith offset), and site-specific ecesis time revealed a total uncertainty value of +/- 5-9 years. Three adjacent terminal moraines were identified, which increasingly tapered towards the glacier, with oldest deposition dates of 1749 +/- 5 CE, 1789 +/- 5 CE, and 1867 +/- 5 CE. Radiocarbon dates of trunks incorporated within the terminal moraine system indicate at least three phases of cumulative glacial activity within the last 2300 years that coincide with the Neoglacial phases of the Southern Patagonian Icefield and adjacent mountain glaciers. The sub-recent trunks revealed the first evidence of a Neoglacial advance between similar to 600 BCE and 100 CE, which so far has not been substantiated in the Magallanes-Tierra del Fuego region.
CRIS-Team WoS Importer:2019-09-17

Late Holocene relative humidity history on the southeastern Tibetan plateau inferred from a tree-ring δ18O record: Recent decrease and conditions during the last 1500 years - Grießinger, Jussi; Bräuning, Achim; Helle, Gerhard; Hochreuther, Philipp; Schleser, Gerhard (Quaternary international, 2017)
Keywords: Climate variability; 1500 year climate reconstruction; Summer monsoon; Relative humidity; Tree-ring δ18O; Tibetan plateau

Late Holocene relative humidity history on the southeastern Tibetan plateau inferred from a tree-ring δ18O record: Recent decrease and conditions during the last 1500 years - Grießinger, Jussi; Bräuning, Achim; Helle, Gerhard; Hochreuther, Philipp; Schleser, Gerhard Hans (Quaternary international, 2017)
In recent decades, the Tibetan plateau (TP) experienced a distinctive temperature increase, with fundamental consequences for the hydrological system. As meteorological time-series extending back more than 60 years are scarce, there is a strong need for proxy data providing insight into the regional hydroclimatic history as well as the long-term variability. Within this study, a recently developed annually resolved 1500 year-long tree-ring stable oxygen isotope (δ18O) time from the southeastern TP is presented. Climate–proxy relationships reveal a strong impact of relative humidity (rH) during the summer months (May to September) on tree-ring δ18O, explaining around 45% of its variance. The derived reconstruction of relative humidity reveals a recent trend towards drier conditions on the TP. However, the present low rH level is not unprecedented in regard to the last 1500 years. In comparison to recent climate conditions, the Medieval Warm Period (MWP) was characterized by more stable conditions with higher humidity values. Hydroclimatic conditions during the Little Ice Age (LIA) suggest a contrasting two-phased period, with a clear shift from drier conditions prevailing between 1400 and 1650 AD to more humid conditions since the second half of the 17th century. Comparisons with other local proxies from lake levels and Pollen data from the southern part of the Tibetan plateau indicate a common regional climate forcing during the MWP and the LIA which can be related to changes in summer monsoon activity. However, the strength of the distinct dryness trend during the 20th century seems unique.
Keywords: Tree-ring δ18O; Tibetan plateau; Relative humidity; Summer monsoon; 1500 year climate reconstruction; Climate variability

Late Holocene variations in monsoon intensity in the Tibetan-Himalayan region - evidence from tree-rings - Grießinger, Jussi; Bräuning, Achim (Journal of the Geological Society of India, 2006)
The knowledge of past climate variability is of great relevance for understanding the dynamics of the climate system. We developed new reconstructions of the variation of summer monsoon intensity in High Asia during the past millennium from a network of tree-ring series from the Tibetan Plateau. We studied several wood parameters which contain information about different seasonal climate signals, i.e., ring width, maximum latewood density and stable carbon isotopes in wood cellulose. In central Tibet, periods of low pre-monsoon rainfall occurred during the second half of the 14th century, around 1600 AD, during the 1880's and the first half of the 20th century. High summer monsoon activity in eastern Tibet occurred between 1220 and 1400 AD and probably corresponds to the "Medieval Warm Period". Several minima in monsoon intensity occurred during the "Little Ice Age" between the first half of the 16th century and the second half of the 18th century. The monsoon intensity after 1980 AD is the highest since the first half of the 17th century. This finding is generally consistent with climate model predictions that suggest an intensification of the summer monsoon with ongoing climate warming. Thus, tree-ring networks can be used as an independent data source for the validation of climate models. The summer monsoon activity is presently still within the range of the natural variability documented during the past thousand years.
UnivIS-Import:2015-03-09:Pub.2006.nat.dgeo.IG.LGIPDT.lateho
Keywords: Dendroclimatology; Maximum latewood density; Rainfall reconstruction; Stable carbon isotopes; Summer monsoon; Tibetan Plateau

Long-term decrease in Asian monsoon rainfall and abrupt climate change events over the past 6,700 years - Yang, Bao; Qin, Chun; Bräuning, Achim; Osborn, Timothy J.; Trouet, Valerie; Ljungqvist, Fredrik Charpentier; Esper, Jan; Schneider, Lea; Grießinger, Jussi; Büntgen, Ulf; Rossi, Sergio; Dong, Guanghui; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Asian summer monsoon (ASM) variability and its long-term ecological and societal impacts extending back to Neolithic times are poorly understood due to a lack of high-resolution climate proxy data. Here, we present a precisely dated and well-calibrated tree-ring stable isotope chronology from the Tibetan Plateau with 1- to 5-y resolution that reflects high- to low-frequency ASM variability from 4680 BCE to 2011 CE. Superimposed on a persistent drying trend since the mid-Holocene, a rapid decrease in moisture availability between ∼2000 and ∼1500 BCE caused a dry hydroclimatic regime from ∼1675 to ∼1185 BCE, with mean precipitation estimated at 42 ± 4% and 5 ± 2% lower than during the mid-Holocene and the instrumental period, respectively. This second-millennium–BCE megadrought marks the mid-to late Holocene transition, during which regional forests declined and enhanced aeolian activity affected northern Chinese ecosystems. We argue that this abrupt aridification starting ∼2000 BCE contributed to the shift of Neolithic cultures in northern China and likely triggered human migration and societal transformation.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Tree rings | stable isotopes | climate variability | megadrought | Asian summer monsoon

Long-term growth trends of Abies delavayi and its physiological responses to a warming climate in the Cangshan Mountains, southwestern China - Yang, Rao Qiong; Zhao, Fan; Fan, Ze Xin; Panthi, Shankar; Fu, Pei Li; Bräuning, Achim; Grießinger, Jussi; Li, Zong Shan (Forest Ecology and Management, 2022)
Long-term tree growth trends and physiological responses to environmental changes, i.e., climate warming, and the rise of atmospheric [CO2] (Ca), need to be investigated across diverse forest ecosystems. We detected long-term trends in tree growth and δ13C derived intrinsic water use efficiency (iWUE) of Abies delavayi in the Cangshan Mountains, at its southern distribution edge in the Hengduan Mountains in southwestern China. We applied a dual-isotopic approach (δ13C, δ18O) to detect the shifts of tree physiological responses (photosynthetic, stomatal conductance) from colder to warmer conditions. Annual basal area increment (BAI) of A. delavayi in the Cangshan Mountains was decreasing since the 1950s, whilst the declining trend of tree growth was not obvious during the earlier period (1800–1951) after removing tree age- and size-related growth signals. Tree growth correlated negatively with temperatures and positively with relative humidity and self-calibrated Palmer drought severity index (scPDSI) during the early growing season (February to June), indicating a predominant growth limitation by moisture availability. Leaf inter-cellular [CO2] (Ci) derived from tree-ring δ13C of A. delavayi increased over time, with a rate slower than atmospheric Ca rise, resulting in a decrease in the Ci/Ca ratio. Intrinsic water-use efficiency (iWUE) was increasing, especially after the 1950s. Dual-isotopic analyses revealed a reduction of stomatal conductance and stable or declined photosynthetic assimilation under warmer and drier environmental conditions. Recent growth decline of A. delavayi in the Cangshan Mountains was mainly related to the increase of warming-mediated drought stress and the resulting stomatal closure, while a positive effect of CO2 fertilization was diminished under warming and drying environmental conditions. Our results serve as an early warning for tree growth and productivity of A. delavayi forests at the southern distribution limits under the ongoing warming climate.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Abies delavayi; Climate change; Growth trends; Hengduan Mountains; Stable isotopes; Tree rings

May–June drought reconstruction over the past 821 years on the south-central Tibetan Plateau derived from tree-ring width series - He, Minhui; Bräuning, Achim; Grießinger, Jussi; Hochreuther, Philipp; Wernicke, Jakob (Dendrochronologia, 2018)
Keywords: Tibetan Plateau; Tree-ring width; Drought variability; South Asian summer monsoon

Multi-centennial reconstruction of drought events in South-Western Iran using tree rings of Mediterranean cypress (Cupressus sempervirens L.) - Arsalani, Mohsen; Grießinger, Jussi; Pourtahmasi, Kambiz; Bräuning, Achim (Palaeogeography, Palaeoclimatology, Palaeoecology, 2021)
Semi-arid regions are among the most vulnerable areas prone to the negative impacts of climate change. Long-term high-resolution proxy climate data will enable us to put the recent climate trends into a long-term context of natural climate variability. We developed the hitherto first regional ring-width chronology (1450–2015C.E.) from Cupressus sempervirens L. in the Zagros Mountains, western Iran and reconstructed precipitation variability for the semi-arid region during the period 1560–2015C.E. Climate-growth relationships revealed that precipitation and minimum temperatures are positively correlated with radial growth, whereas maximum temperatures reveal negative impacts. Spatial correlations with gridded precipitation data, Palmer drought severity index (PDSI), and standardized precipitation-evapotranspiration index (SPEI 01) further indicate that the climate signals contained in tree-ring width variations capture the precipitation variability in the Near East and other eastern Mediterranean regions. The southern Zagros Mts. experienced multiple megadroughts during the reconstructed period. The longest dry period occurred from 1956 to 1971 and the highest frequency of dry events occurred in the 20th century. In addition, documented famines in Iran occurred within prolonged droughts. The southern Zagros Mts. has experienced high frequency of extreme/severe dry events and long dry phases during the Little Ice Age (1560–1850C.E.). The reconstructed dry and wet events occurred irregularly, and one-year and two-year drought/wet events showed the highest frequency during the reconstructed period, highlighting the importance of sustainable water management strategies for the semi-arid southern Zagros region.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Climate change; Cupressus sempervirens; Dendroclimatology; Little Ice Age; Teleconnection patterns; Zagros Mountains

Multi-century humidity reconstructions from the southeastern Tibetan Plateau inferred from tree-ring δ18O - Wernicke, Jakob; Hochreuther, Philipp; Grießinger, Jussi; Zhu, Haifeng; Wang, Lily; Bräuning, Achim (Global and Planetary Change, 2017)
Keywords: Little Ice Age; Tree-ring δ18O; Southeastern Tibetan Plateau; Teleconnections

Naturgefahren und Naturgefahrenmanagement im Oberen Paznauntal/Tirol. - Titz, Alexandra; Grießinger, Jussi (Mitteilungen der Fränkischen Geographischen Gesellschaft Band 61/62, 2016)
Naturgefahren wie Hochwasser, Massenbewegungen, Lawinen oder Erdbeben fordern alljährlich zahlreiche Menschenleben und verursachen Schäden in Milliardenhöhe. Die Bedrohung durch die Natur hat sich in den letzten Jahrhunderten nicht grundlegend geändert, dennoch war und ist der Umgang mit Naturgefahren einem stetigen Wandel unterworfen. Trotz der präzisen Erforschung der geophysikalischen Prozesse und Innovationen im technischen Bereich, die neben einer verbesserten Vorhersage, Frühwarnung und Kommunikation auch effektivere Schutzmaßnahmen ermöglichen, scheint die Verwundbarkeit und Risikoanfälligkeit der Menschen in gleichem Maße anzuwachsen. Am Beispiel der Alpengemeinde Galtür in Tirol/Österreich, in der sich 1999 ein schweres  Lawinenereignis zutrug, soll der Umgang mit Naturgefahren exemplarisch nachgezeichnet werden. Dazu fließen auch Ergebnisse eines projektorientierten Hauptseminars ein, die Studierende der Bachelorstudiengänge Kulturgeographie und Physische Geographie im Rahmen von empirischen Erhebungen und Expertengesprächen vor Ort in Galtür gewonnen haben.
Keywords: Naturgefahren; Naturgefahrenmanagement; Geographische Hazardforschung; Alpen; Paznauntal; Galtür; Lawine; Gefahrenzonenplan

New perspective on spring vegetation phenology and global climate change based on Tibetan Plateau tree-ring data. - Yang, Bao; He, Minhui; Shishov, Vladimir; Rossi, Sergio; Vaganov, Eugene; Tychkov, Ivan; Ljungqvist, Frederik; Bräuning, Achim; Grießinger, Jussi (Proceedings of the National Academy of Sciences of the United States of America, 2017)
Phenological responses of vegetation to climate, in particular to the ongoing warming trend, have received much attention. However, divergent results from the analyses of remote sensing data have been obtained for the Tibetan Plateau (TP), the world's largest high-elevation region. This study provides a perspective on vegetation phenology shifts during 1960-2014, gained using an innovative approach based on a well-validated, process-based, tree-ring growth model that is independent of temporal changes in technical properties and image quality of remote sensing products. Twenty composite site chronologies were analyzed, comprising about 3,000 trees from forested areas across the TP. We found that the start of the growing season (SOS) has advanced, on average, by 0.28 d/y over the period 1960-2014. The end of the growing season (EOS) has been delayed, by an estimated 0.33 d/y during 1982-2014. No significant changes in SOS or EOS were observed during 1960-1981. April-June and August-September minimum temperatures are the main climatic drivers for SOS and EOS, respectively. An increase of 1 °C in April-June minimum temperature shifted the dates of xylem phenology by 6 to 7 d, lengthening the period of tree-ring formation. This study extends the chronology of TP phenology farther back in time and reconciles the disparate views on SOS derived from remote sensing data. Scaling up this analysis may improve understanding of climate change effects and related phenological and plant productivity on a global scale.

No evidence for carryover effect in tree rings based on a pulse-labelling experiment on Juniperus communis in South Germany - He, Minhui; Bräuning, Achim; Rossi, Sergio; Gebrekirstos, Aster; Grießinger, Jussi; Mayr, Christoph; Peng, Changhui; Yang, Bao (Trees-Structure and Function, 2020)
Key message: A clear carryover effect of tree-ring formation was not detected based on a pulse-labelling experiment conducted on Juniperus communis in South Germany. Abstract: The inherent linkage between photosynthesis and the formation of wood is important for the understanding of relationships between tree-ring series and climate/environmental data in dendroclimatology studies. However, it is impossible to reach a mechanistic procedure of tree stem radial growth depending on its carbon balance from a traditional statistical point of view alone. Pulse labelling experiment with stable carbon isotope (13CO2) has provided innovative insights into the fate of recently assimilated carbon in organs and carbon-containing compounds. In this study, we conducted an in situ pulse labelling experiment on 27 July 2016 to examine the response of tree ring and different-aged needles to short-term elevated 13CO2 of a juniper shrub growing on a heathland in South Germany. New and old needles from four expositions were sampled before and after the experiment. A wood segment was taken from the main branch and stable carbon isotope composition (δ13C) was analysed at an intra-annual time scale. Before the experiment, the mean δ13C was − 26.8 ± 0.4‰ (mean ± standard deviation) for both needle ages, while woody tissue showed about 3‰ higher δ13C compared to needles. Substantial enriched 13C was detected in the needles after the experiment. New needles showed significant higher δ13C than the old ones 1–7 days after the experiment. Significant enriched δ13C was detected in the wood from 35 to 61% of the annual tree ring in 2016, indicating that the short-term enrichment of 13C can affect wood formation for a large section. No enhancement in 13C signal appeared in the tree ring of the subsequent year 2017, suggesting the absence of a carryover effect. Wood formation did not reply on the carbohydrates stored even 1 year before and thus tree-ring ecophysiological modelling as well as dendrochronological studies should therefore benefit from such result.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Carryover effect; Dendrochronology; Needle ages; Shrub species; Stable carbon isotope

On the influence of autocorrelation on the significance of wavelet spectral peaks - Hochreuther, Philipp; Wernicke, Jakob; Grießinger, Jussi; Bräuning, Achim (Proceedings of the DENDROSYMPOSIUM 2016, 2017)

Permafrost Biases Climate Signals in delta O-18(tree-ring) Series from a Sub-Alpine Tree Stand in Val Bever/Switzerland - Grießinger, Jussi; Meier, Wolfgang; Bast, Alexander; Debel, Annette; Gaertner-Roer, Isabelle; Gaertner, Holger (Atmosphere, 2021)
During recent decades, stable oxygen isotopes derived from tree-ring cellulose (delta O-18(TRC)) have been frequently utilised as the baseline for palaeoclimatic reconstructions. In this context, numerous studies take advantage of the high sensitivity of trees close to their ecological distribution limit (high elevation or high latitudes). However, this increases the chance that indirect climatic forces such as cold ground induced by permafrost can distort the climate-proxy relationship. In this study, a tree stand of sub-alpine larch trees (Larix decidua Mill.) located in an inner alpine dry valley (Val Bever), Switzerland, was analysed for its delta O-18(TRC) variations during the last 180 years. A total of eight L. decidua trees were analysed on an individual base, half of which are located on verified sporadic permafrost lenses approximately 500 m below the expected lower limit of discontinuous permafrost. The derived isotope time series are strongly dependent on variations in summer temperature, precipitation and large-scale circulation patterns (geopotential height fields). The results demonstrate that trees growing outside of the permafrost distribution provide a significantly stronger and more consistent climate-proxy relationship over time than permafrost-affected tree stands. The climate sensitivity of permafrost-affected trees is analogical to the permafrost-free tree stands (positive and negative correlations with temperature and precipitation, respectively) but attenuated partly leading to a complete loss of significance. In particular, decadal summer temperature variations are well reflected in delta O-18(TRC) from permafrost-free sites (r = 0.62, p < 0.01), while permafrost-affected sites demonstrate a full lack of this dependency (r = 0.30, p > 0.05). Since both tree stands are located just a few meters away from one another and are subject to the same climatic influences, discrepancies in the isotope time series can only be attributed to variations in the trees' source water that constraints the climatic fingerprints on delta O-18(TRC). If the two individual time series are merged to one local mean chronology, the climatic sensitivity reflects an intermediate between the permafrost-free and -affected delta O-18(TRC) time series. It can be deduced, that a significant loss of information on past climate variations arises by simply averaging both tree stands without prior knowledge of differing subsurface conditions.
CRIS-Team WoS Importer:2021-08-06

Persistent humid climate favored the Qin and Western Han Dynasties in China around 2,200 y ago - Qin, Chun; Yang, Bao; Bräuning, Achim; Ljungqvist, Fredrik Charpentier; Osborn, Timothy J.; Shishov, Vladimir; He, Minhui; Kang, Shuyuan; Schneider, Lea; Esper, Jan; Büntgen, Ulf; Grießinger, Jussi; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2025)
The Qin and Western Han dynasties (221 BCE to 24 CE) represent an era of societal prosperity in China. However, due to a lack of high-resolution paleoclimate records it is still unclear whether the agricultural boost documented for this period was associated with more favorable climatic conditions. Here, multiparameter analysis of annually resolved tree-ring records and process-based physiological modeling provide evidence of stable and consistently humid climatic conditions during 270 to 77 BCE in northern China. Precipitation in the Asian summer monsoon region during the Qin–Western Han Dynasties was 18 to 34% higher compared to present-day conditions. In shifting agricultural and pastoral boundaries 60 to 100 km northwestward, possibility up to 200 km at times, persistently wetter conditions arguably increased food production, contributing to the socioeconomic prosperity around 2,200 y ago. A gradual wetting trend in the western part of arid northwestern China since the 1980s resembles the historical climate analogue, suggesting that similar benefits for regional environmental and agricultural systems may reoccur under current climate change, at least in the near term.
CRIS-Team Scopus Importer:2025-01-31
Keywords: ancient dynasties; Asian summer monsoon; climate impacts; climate reconstruction; climate variability

Physisch-Geographisches Geländepraktikum - Bräuning, Achim; Bäumler, Rupert; Feick, Sebastian; Grießinger, Jussi (FAU Erlangen-Nürnberg, Institut für Geographie, 2012)
Keywords: Geografiestudium; Physische Geografie; Raumbeobachtung

Preliminary results from ring width and latewood density measurements from the southeast Tibetan Plateau, China - Hochreuther, Philipp; Grießinger, Jussi; Bräuning, Achim (TRACE - Tree Rings in Archaeology, Climatology and Ecology, Vol. 10: Proceedings of the DENDROSYMPOSIUM 2011 Scientific Technical Report STR 12/03, GFZ Potsdam, 2012)

Process-based modeling of tree-ring formation and its relationships with climate on the Tibetan Plateau - He, Minhui; Shishov, Vladimir; Kaparova, Nazgul; Yang, Bao; Bräuning, Achim; Grießinger, Jussi (Dendrochronologia, 2017)
Keywords: Soil moisture content; Temperature; Process-based modeling; VS-oscilloscope; Tibetan Plateau; Tree-ring formation

Projections for the changes in growing season length of tree-ring formation on the Tibetan Plateau based on CMIP5 model simulations - He, Minhui; Yang, Bao; Shishov, Vladimir; Rossi, Sergio; Bräuning, Achim; Ljungqvist, Fredrik Charpentier; Grießinger, Jussi (International Journal of Biometeorology, 2018)
Keywords: Climate predictions; Temperature sensitivity; Phenology; Representative Concentration Pathways

Projections for the changes in growing season length of tree-ring formation on the Tibetan Plateau based on CMIP5 model simulations - He, Minhui; Yang, Bao; Shishov, Vladimir; Rossi, Sergio; Bräuning, Achim; Ljungqvist, Fredrik Charpentier; Grießinger, Jussi (International Journal of Biometeorology, 2018)
The response of the growing season to the ongoing global warming has gained considerable attention. In particular, how and to which extent the growing season will change during this century is essential information for the Tibetan Plateau, where the observed warming trend has exceeded the global mean. In this study, the 1960–2014 mean length of the tree-ring growing season (LOS) on the Tibetan Plateau was derived from results of the Vaganov-Shashkin oscilloscope tree growth model, based on 20 composite study sites and more than 3000 trees. Bootstrap and partial correlations were used to evaluate the most significant climate factors determining the LOS in the study region. Based on this relationship, we predicted the future variability of the LOS under three emission scenarios (Representative Concentration Pathways (RCP) 2.6, 6.0, and 8.5, representing different concentrations of greenhouse gasses) derived from 17 Earth system models participating in the Coupled Model Intercomparison Project Phase 5 (CMIP5). The averaged LOS on the Tibetan Plateau is 103 days during the period 1960–2014, and April–September minimum temperature is the strongest factor controlling the LOS. We detected a general increase in the LOS over the twenty-first century under all the three selected scenarios. By the middle of this century, LOS will extend by about 3 to 4 weeks under the RCPs 2.6 and 6.0, and by more than 1 month (37 days) under the RCP 8.5, relative to the baseline period 1960–2014. From the middle to the end of the twenty-first century, LOS will further extend by about 3 to 4 weeks under the RCPs 6.0 and 8.5, respectively. Under the RCP 2.6 scenario, however, the extension reaches a plateau at around 2050 and about 2 weeks LOS extension. In total, we found an average rate of 2.1, 3.6, and 5.0 days decade−1 for the LOS extension from 2015 to 2100 under the RCPs 2.6, 6.0, and 8.5, respectively. However, such estimated LOS extensions may be offset by other ecological factors that were not included into the growth model. The estimated lengthening of the growing season could substantially affect carbon sequestration and forest productivity on the Tibetan Platea
Keywords: Phenology; Temperature; sensitivity; Representative; Concentration; Pathways; Climate; predictions

Recent advances in dendroclimatology in China - He, Minhui; Yang, Bao; Bräuning, Achim; Rossi, Sergio; Ljungqvist, Fredrik Charpentier; Shishov, Vladimir; Grießinger, Jussi; Wang, Jianglin; Liu, Jingjing; Qin, Chun (Earth-Science Reviews, 2019)
Considerable progress has been made in dendroclimatological research in China during the period 2000–2017, including a significant increase in the spatial coverage of tree-ring chronologies developed for paleoclimatic research. New tree-ring sampling sites have been established across the Tibetan Plateau, as well as the northeastern and sub-tropical eastern parts of China. Most of the studies use coniferous trees, although different plant functional types (e.g., broadleaf species and shrubs) have also been increasingly investigated. Tree-ring chronologies longer than 600 years, however, are mostly found on the Tibetan Plateau, with the longest one extending back to 2637 BCE (before Common Era). Most tree-ring records in the eastern parts of China are <400 years long. Tree-ring width is the most commonly studied parameter, although stable isotope ratios and wood density data have also been obtained for specific sites. Stable oxygen isotope data frequently shares a common hydroclimate signal, whereas the climate or environmental signals remain inconsistent for the few available stable carbon isotope records. In general, tree-ring width-based temperature reconstructions originate from higher elevation sites (i.e., treeline) compared to hydroclimate reconstructions. Precipitation or drought reconstructions are mainly obtained from regions with an annual precipitation of <800 mm. Most of the tree-ring reconstructions are based on individual site or local-scale chronologies, although a limited number of regional-scale and field reconstructions have been produced. The most prominent identified characteristics of the recent advances in dendroclimatological research for China have manifested in aspects such as an expanded network of sampling sites, improved climate reconstruction methodology, and improved uncertainty estimations in the latter. Furthermore, the traditional statistical-based tree growth–climate relationships have been supplemented by monitoring and modeling approaches. Based on the progress from 2000 to 2017, and on the research potential of the country in this field, we expect additional widening of the dendroclimatological investigations in China during the coming years.
CRIS-Team Scopus Importer:2019-05-28
Keywords: China; Climate change; Dendroclimatology; Hydroclimate reconstructions; Temperature reconstructions; Tree growth

Reconstructing glacier retreat since the Little Ice Age in SE Tibet by glacier mapping and equilibrium line altitude calculation. - Loibl, David; Lehmkuhl, Frank; Grießinger, Jussi (Geomorphology, 2014)
<span style="color: rgb(46, 46, 46); font-family: 'Arial Unicode MS', 'Arial Unicode', Arial, 'URW Gothic L', Helvetica, Tahoma, 'Cambria Math', sans-serif; font-size: 13px; line-height: 20px; text-align: justify; word-spacing: -1.010229468345642px;">Temperate glaciers in the eastern Nyainqêntanglha Range, southeastern Tibet, are highly sensitive to climate change and therefore of particular high interest for research on late Holocene changes of the monsoonal climate in High Asia. However, because of the remoteness of the area, the scarcity of empirical data, and the challenges to remote sensing work posed by cloud and snow cover, knowledge about the glacier dynamics and changes in this region is still very limited. In this study, we applied a remote sensing approach in which 1964 glaciers were mapped from a Landsat ETM+ scene and subsequently parameterized by DEM-supported measurements. Geomorphological evidence, i.e., trimlines and latero-frontal moraines, were used to obtain quantitative data on the glaciers' morphological characteristics and the changes since the Little Ice Age (LIA) maximum glacier advance. Statistical analysis of glacier length change revealed an average retreat of  27% and a trend toward stronger retreat for smaller glaciers. An evaluation of different methods to calculate equilibrium line altitudes (ELAs) indicates that an optimized toe-to-ridge altitude method (TRAM) is more suitable than other methods in settings with complex topography and a lack of mass balance measurements. A large number of glacier measurements are crucial for high quality of TRAM results, and special attention has to be paid to different glacier characteristics. In order to determine the best-fitting TRAM ratio value and to test the quality of the calculated ELAs, a remote sensing approach was applied: for each investigated glacier, the altitudes of transient snowlines visible in the late summer Landsat scene were measured from the DEM and compared to TRAM results. The interpolated ELA results show a SE–NW gradient ranging from 4400 to 5600 m asl and an average ELA rise of  136 m since the LIA. Because of the high spatial resolution of measurements, the ELA distribution reveals topographic effects down to the catchment scale, specifically orographic rainfall and leeward shielding. The interpretation of these patterns reveals that the eastern Nyainqêntanglha Range is influenced by both, the Indian (ISM) and East Asian summer monsoon (EASM). However, the EASM does not reach the western part of the study area. The results indicate that the monsoonal temperate glaciers' high sensitivity to climate change is driven by two double forcings owing to the coincidence of accumulation and ablation phases.
Keywords: Glacier retreat; Equilibrium line altitude; Remote sensing; GIS; Little Ice Age; Southeastern Tibet

Relationships between ring width and maximum latewood density – an example from southeast Tibet - Hochreuther, Philipp; Münchow, Jannes; Grießinger, Jussi; Bräuning, Achim (TRACE - Tree Rings in Archaeology, Climatology and Ecology, Vol. 11: Proceedings of the DENDROSYMPOSIUM 2012 Scientific Technical Report STR13/05, GFZ Potsdam, 2013)

Relationships betweenwood formation and cambium phenology on the Tibetan plateau during 1960-2014 - He, Minhui; Yang, Bao; Shishov, Vladimir; Rossi, Sergio; Bräuning, Achim; Ljungqvist, Fredrik Charpentier; Grießinger, Jussi (Forests, 2018)
Keywords: Dendroclimatology; Forest ecosystems; Conifers; Tree-ring; Xylogenesis; Growing season; Growth

Reply to Weiss: Tree-ring stable oxygen isotopes suggest an increase in Asian monsoon rainfall at 4.2 ka BP - Yang, Bao; Qin, Chun; Bräuning, Achim; Osborn, Timothy J.; Trouet, Valerie; Ljungqvist, Fredrik Charpentier; Esper, Jan; Schneider, Lea; Grießinger, Jussi; Büntgen, Ulf; Rossi, Sergio; Dong, Guanghui; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2022)
CRIS-Team Scopus Importer:2022-05-27

Rising utilization of stable isotopes in tree rings for climate change and forest ecology - Huang, Ru; Xu, Chenxi; Grießinger, Jussi; Feng, Xiaoyu; Zhu, Haifeng; Bräuning, Achim (Journal of Forestry Research, 2024)
Analyses of stable isotopes (C, O, H) in tree rings are increasingly important cross-disciplinary programs. The rapid development in this field documented in an increasing number of publications requires a comprehensive review. This study includes a bibliometric analysis-based review to better understand research trends in tree ring stable isotope research. Overall, 1475 publications were selected from the Web of Science Core Collection for 1974–2023. The findings are that: (1) numbers of annual publications and citations increased since 1974. From 1974 to 1980, there were around two relevant publications per year. However, from 2020 to 2022, this rose sharply to 109 publications per year. Likewise, average article citations were less than four per year before 1990, but were around four per article per year after 2000; (2) the major subjects using tree ring stable isotopes include forestry, geosciences, and environmental sciences, contributing to 42.5% of the total during 1974–2023; (3) the top three most productive institutions are the Chinese Academy of Sciences (423), the Swiss Federal Institute for Forest, Snow and Landscape Research (227), and the University of Arizona (204). These achievements result from strong collaborations; (4) review papers, for example, (Dawson et al., Annu Rev Ecol Syst 33:507–559, 2002) and (McCarroll and Loader, Quat Sci Rev 23:771–801, 2004), are among the most cited, with more than 1000 citations; (5) tree ring stable isotope studies mainly focus on climatology and ecology, with atmospheric CO2 one of the most popular topics. Since 2010, precipitation and drought have received increasing attention. Based on this analysis, the research stages, key findings, debated issues, limitations and directions for future research are summarized. This study serves as an important attempt to understand the progress on the use of stable isotopes in tree rings, providing scientific guidance for young researchers in this field.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Bibliometric; Stable isotopes; Tree rings; Web of Science

Spring season in western nepal himalaya is not yet warming: A 400-year temperature reconstruction based on tree-ringwidths of Himalayan Hemlock (Tsuga Dumosa) - Aryal, Sugam; Gaire, Narayan Prasad; Pokhrel, Nawa Raj; Rana, Prabina; Sharma, Basant; Kharal, Deepak Kumar; Poudel, Buddi Sagar; Dyola, Nita; Fan, Ze Xin; Grießinger, Jussi; Bräuning, Achim (Atmosphere, 2020)
The Himalayan region has already witnessed profound climate changes detectable in the cryosphere and the hydrological cycle, already resulting in drastic socio-economic impacts. We developed a 619-yea-long tree-ring-width chronology from the central Nepal Himalaya, spanning the period 1399-2017 CE. However, due to low replication of the early part of the chronology, only the section after 1600 CE was used for climate reconstruction. Proxy climate relationships indicate that temperature conditions during spring (March-May) are the main forcing factor for tree growth of Tsuga dumosa at the study site. We developed a robust climate reconstruction model and reconstructed spring temperatures for the period 1600-2017 CE. Our reconstruction showed cooler conditions during 1658-1681 CE, 1705-1722 CE, 1753-1773 CE, 1796-1874 CE, 1900-1936 CE, and 1973 CE. Periods with comparably warmer conditions occurred in 1600-1625 CE, 1633-1657 CE, 1682-1704 CE, 1740-1752 CE, 1779-1795 CE, 1936-1945 CE, 1956-1972 CE, and at the beginning of the 21st century. Tropical volcanic eruptions showed only a sporadic impact on the reconstructed temperature. Also, no consistent temperature trend was evident since 1600 CE. Our temperature reconstruction showed positive teleconnections with March-May averaged gridded temperature data for far west Nepal and adjacent areas in Northwest India and on the Southwest Tibetan plateau. We found spectral periodicities of 2.75-4 and 40-65 years frequencies in our temperature reconstruction, indicating that past climate variability in central Nepal might have been influenced by large-scale climate modes, like the Atlantic Multi-decadal Oscillation, the North Atlantic Oscillation, and the El Nino-Southern Oscillation.
CRIS-Team Scopus Importer:2020-03-20
Keywords: Climate variability; Dendroclimatology; Manang; Past climate; Pre-monsoon temperature

Stable oxygen isotopes in juniper trees from the Tibetan plateau as a proxy for monsoonal activity - Grießinger, Jussi; Bräuning, Achim; Thomas, Axel; Schleser, Gerhard Hans (TRACE - Tree Rings in Archaeology, Climatology and Ecology, Vol. 6: Proceedings of the DENDROSYMPOSIUM 2007 Scientific Technical Report STR 08/05, GFZ Potsdam, 2008)
UnivIS-Import:2015-03-09:Pub.2008.nat.dgeo.IG.LGIPDT.stable

Temperature signals in tree-ring oxygen isotope series from the northern slope of the Himalaya - Huang, Ru; Zhu, Haifeng; Liang, Eryuan; Grießinger, Jussi; Wernicke, Jakob; Yu, Wusheng; Hochreuther, Philipp; Risi, Camille; Zeng, Yijian; Fremme, Astrid; Sodemann, Harald; Bräuning, Achim (Earth and Planetary Science Letters, 2019)
Keywords: westerlies; tree ring; South Asian Summer Monsoon; ice core; oxygen isotope; Himalaya

The 1820s Marks a Shift to Hotter-Drier Summers in Western Europe Since 1360 - Wang, Lu; Liu, Hongyan; Chen, Deliang; Zhang, Peng; Leavitt, Steven; Liu, Yu; Fang, Congxi; Sun, Changfeng; Cai, Qiufang; Gui, Zhengyang; Liang, Boyi; Shi, Liang; et al. (Geophysical Research Letters, 2022)
Recent soil moisture (SM) reconstructions revealed plunging trends and enhanced SM-temperature couplings over the last two decades in dry regions. However, how SM changed and whether the land-atmosphere interaction was intensified over time in humid regions remained unknown. Here we reported the first six-century-long regional summer SM reconstruction (1360-2000 CE) in western Europe (WE) using three individual tree-ring delta O-18 chronologies in England and France. A sharp wet-to-dry change occurred around 1820, earlier than 1850-1900 CE, the commonly used historical baseline of anthropogenic climate changes. Enhanced coupling of SM-temperature followed, with stronger summer sea level pressure anomalies in dry years after the 1820s. Our results reveal that the hotter-drier regime has also become more frequent in humid WE under global warming.
CRIS-Team WoS Importer:2022-08-26

The impact of warming climate on Himalayan silver fir growth along an elevation gradient in the Mt. Everest region - Gaire, Narayan Prasad; Zaw, Zaw; Bräuning, Achim; Grießinger, Jussi; Sharma, Bimal; Rana, Prabina; Bhandari, Sanjaya; Basnet, Saroj; Fan, Ze Xin (Agricultural and Forest Meteorology, 2023)
The impacts of rapid climate change in the Himalayan region on growth and sensitivity of tree species across their entire elevation distribution range are not well understood. This study investigates the growth and climate sensitivity of the endemic species Himalayan silver fir (Abies spectabilis, D.Don) along an elevation gradient in the sub-alpine belt in the Mt. Everest region. We developed tree ring-width chronologies, spanning 98 to 310 years, from six sites along an elevation gradient (3400–4100 m a.s.l.). The growth of Himalayan silver fir is primarily limited by low temperatures during the growing season and moisture availability during spring. Significant positive correlations were found between tree growth and mean, minimum and maximum temperatures for most parts of the vegetation period except spring. In contrast, significant positive correlations are apparent for precipitation, self-calibrated Palmer drought severity index (scPDSI), and standardized precipitation-evapotranspiration index (SPEI) during the spring season (March–May) at most of the elevations except for the upper treeline site. Thus, low summer temperatures are the primary limiting factor at all investigated elevations, while moisture supply during spring triggers growth variations at low- to mid-elevations. The long-term growth trends of A. spectabilis have decreased at low- to mid-elevation sites but increased at the treeline during the period 1981–2011. Warming and intensified moisture stress during spring could have negative effects on tree growth, potentially resulting in growth decline and forest dieback at middle and low elevations. These findings emphasize the importance of understanding the vulnerability of forests at middle and low elevations to future climate change.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Climate change; Climate sensitivity; Elevation gradient; Growth trend; Himalayan silver fir (Abies spectabilis); Tree ring

The influence of decision-making in tree ring-based climate reconstructions - Büntgen, Ulf; Allen, Kathy; Anchukaitis, Kevin J; Arseneault, Dominique; Boucher, Étienne; Bräuning, Achim; Chatterjee, Snigdhansu; Cherubini, Paolo; Churakova (Sidorova), Olga V; Corona, Christophe; Gennaretti, Fabio; Grießinger, Jussi; et al. (Nature Communications, 2021)

Tree-ring-based seasonal temperature reconstructions and ecological implications of recent warming on oak forest health in the Zagros Mountains, Iran - Arsalani, Mohsen; Grießinger, Jussi; Bräuning, Achim (International journal of biometeorology, 2022)
Abrupt changes in temperature have especially strong impacts on fragile ecosystems located in semi-arid regions. In this study, we analyzed tree-ring widths (TRW) of Mediterranean cypress (Cupressus sempervirens var. horizontalis) in the Zagros Mountains, Iran. Furthermore, we separately measured earlywood width (EWW) and latewood width (LWW) of Persian oak (Quercus brantii Lindl.) to examine if intra-annual resolution of tree-ring parameters of Q. brantii tree rings can be used as high-resolution paleoclimate proxies. Climate-growth relationships revealed that mean monthly maximum temperatures (Tmax) are a dominant factor determining radial tree growth and negatively affect both oak and cypress in the Zagros Mountains. Accordingly, we reconstructed two different seasonal windows of past Tmax variability, namely, January–March and June–August over the periods 1860–2015 and 1560–2015, respectively. Regime shift detection identified twelve warm and nine cold significant regime shifts in our summer Tmax reconstructions. The longest hot summer period occurred in the twentieth century, and two warm regime shifts occurred in 1999 and 2008. The highest values of the warm summer regime shift index occurred in 2008, which coincided with fungal pathogen attacks and insect outbreak of the oak leaf roller moth (Tortrix viridana L.) in the Zagros oak woodlands. Interestingly, we found common warm and cold periods in historic climate variability between the summer and winter Tmax reconstructions. Warm and cold regime shifts occurred simultaneously from 1955 to 2015, and significant regional warm summer and winter regime shifts have occurred between 2008 and 2015. The winter and summer Tmax reconstructions show high spatial correlations with large areas in West Asia, North Africa, and the eastern Mediterranean region. Our results strengthen initial studies on past climate variability in Iran and contribute to an enhanced understanding of past temperature variability in West Asia.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Earlywood width; Insect outbreak; Mediterranean cypress; Temperature reconstruction; Tree-ring width; Zagros oak woodland

Tree-ring cellulose oxygen isotopes indicate atmospheric aridity in the western Kunlun Mountains - Feng, Xiaoyu; Huang, Ru; Zhu, Haifeng; Liang, Eryuan; Bräuning, Achim; Zhong, Linhao; Gong, Zhaohui; Zhang, Peng; Asad, Fayaz; Zhu, Xiaolong; Grießinger, Jussi (Ecological Indicators, 2022)
As an important indicator of atmospheric aridity, the vapor pressure deficit (VPD) is being paid increasing attention in global change researches during recent decades. However, available proxy data with the capability to represent VPD is still scarce in the globe. Herein we demonstrated a “hidden” frequency-dependent indication of tree-ring cellulose oxygen isotope (δ18OTRC) to atmospheric aridity in the western Kunlun Mountains, Central Asia. In applying correlation and partial correlation analysis, frequency-dependent climatic drivers triggering the δ18OTRC values were detected. For the raw data with inter-decadal variability, δ18OTRC variations mainly indicated May–August precipitation (Local: r = –0.59, p < 0.001; Moisture source: r = –0.53, p < 0.001), evapotranspiration (ET) (Local: r = –0.57, p < 0.001; Moisture source: r = –0.51, p < 0.001). After a 5-year high-pass filter, the δ18OTRC series revealed highly significant correlation with May–August VPD (Local: r = 0.82, p < 0.001; Moisture source: r = 0.80, p < 0.001). The partial correlation further confirmed the strong linkages with high-frequency VPD when the impact of any additional eco-climatological variable (precipitation, temperature, ET, soil moisture 0–40 cm) was excluded. In contrast, if the effect of May–August VPD was excluded, relationships between δ18OTRC and other variables turned insignificant. Collectively, it was concluded that δ18OTRC from the western Kunlun Mountains may indicate VPD at timescales < 5 years. Our results suggest that frequency-dependent climatic significances should be considered when interpreting multi-process determined δ18OTRC as a climate-proxy.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Atmospheric aridity; Frequency-dependency; Tree-ring cellulose δ; Vapor pressure deficit; Western Kunlun Mountains

Tree-ring dating of lateral and terminal Little Ice Age moraines of four glaciers in southeast Tibet - Hochreuther, Philipp; Loibl, David; Wernicke, Jakob; Grießinger, Jussi; Zhu, Haifeng; Bräuning, Achim (TRACE - Tree Rings in Archaeology, Climatology and Ecology, Vol. 13: Proceedings of the DENDROSYMPOSIUM 2014 Scientific Technical Report 15/06, GFZ Potsdam, 2013)

Tree-Ring Oxygen Isotope Variations in Subalpine Firs from the Western Himalaya Capture Spring Season Temperature Signals - Chinthala, Bency David; Grießinger, Jussi; Ranhotra, Parminder Singh; Tomar, Nidhi; Singh, C. P.; Bräuning, Achim (Forests, 2022)
We analyzed the tree-rings δ18 O of Abies spectabilis (fir) growing at the subalpine treeline ecotone in the Magguchatti valley. The valley is located in the Indian summer monsoon (ISM) dominated region of western Himalaya and also receives snow precipitation derived by westerly disturbances (WDs) during the winter months. The 60 year developed (1960–2019 CE) tree-ring δ18 O chronology revealed a strong positive correlation with the temperature of late winter and spring months (February to April). Strong negative correlations are also apparent for snowcover, soilmoisture, and relative humidity for the same spring season. Our findings partly contrast the significant correlation results of tree-ring δ18 O with summer precipitation and drought indices recorded from other summer monsoon-dominated regions in the Himalayas. The spatial correlation analyses with sea surface temperatures (SSTs) and climate parameters showed subdued signals of tropical Pacific at the site, but with a shift to more moisture influx from the Arabian Sea during the last two decades. Moreover, a significant negative correlation with North Atlantic Oscillation further justifies the strongly captured spring temperature and snowcover signals and the weak effect of summer precipitation in fir trees. A temperature rising trend during the latter half of the 20th century and the elevation effect are taken as important factors controlling the moisture source at the treeline ecotone zones.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Abies spectabilis; Indian summer monsoon; Snowcover; Soil-moisture; Spring temperature; Winter westerlies

Tree rings reveal globally coherent signature of cosmogenic radiocarbon events in 774 and 993 CE - Buntgen, Ulf; Wacker, Lukas; Galvan, J. Diego; Arnold, Stephanie; Arseneault, Dominique; Baillie, Michael; Beer, Jurg; Bernabei, Mauro; Bleicher, Niels; Boswijk, Gretel; Bräuning, Achim; Carrer, Marco; et al. (Nature Communications, 2018)

Tree-ring δ18Ocellulose variations in two Nothofagus species record large-scaleclimatic signals in the South American sector of the Southern Ocean - Soto Rogel, Pamela; Aravena, Juan Carlos; Villalba, Ricardo; Meier, Wolfgang; Grießinger, Jussi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)
In recent decades, southernmost South America (50–56° S) has experienced marked climate change (regional warming, decreased precipitation, reduced snow cover, and increased frequency of heat waves) related to variations in atmospheric circulation over varied timescales. In this paper, we develop oxygen isotopes from tree-ring cellulose (δ18OTRC) as a proxy for climate and atmospheric circulation in order to extend the regional meteorological record to deeper time intervals. Our work focuses on Nothofagus forests in two areas: (i) deciduous N. pumilio forest in the steppe transition zone near Punta Arenas and (ii) humid evergreen N. betuloides forest in the Navarino Island region. To investigate the potential for reconstructing palaeoclimate, δ18OTRC variations were correlated with local climate parameters as well as regional (Amundsen Sea Low, ASL) and hemispheric (Antarctic Oscillation, AAO) atmospheric circulation modes for the last 60 years. N. betuloides δ18OTRC variations show an overall positive trend, indicating isotopic enrichment over the study period, whereas no trend is recorded for the N. pumilio record. The strongest relationships with climate, together with the widest spatial representativeness, occur in the N. betuloides chronology during the growing season (spring to austral summer) and extend spatially from mid to high latitudes. In contrast, the sensitivity of the records is limited to summer months, and spatial correlations are much more limited. In addition, the N. betuloides record shows greater potential for reconstructing local climate features such as soil water (r = − 0.76), wind speed (r = 0.69), and precipitation (r = − 0.66), as well as regional (ASL, r = − 0.80) and hemispheric (AAO, r = 0.77) patterns of extratropical atmospheric circulation. Overall, we conclude that the N. betuloides record represents the most valuable tree-ring climate proxy for southernmost South America over past centuries.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Amundsen Sea Low (ASL); Antarctic Oscillation (AAO); Nothofagus betuloides; Nothofagus pumilio; Southernmost South America (SSA); Tree-ring δ

Trees record changes of the temperate glaciers on the Tibetan Plateau: Potential and uncertainty - Zhu, Haifeng; Shao, Xuemei; Zhang, Hui; Asad, Fayaz; Sigdel, Shalik Ram; Huang, Ru; Li, Yanan; Liu, Wenwen; Muhammad, Sher; Hussain, Iqtidar; Grießinger, Jussi; Liang, Eryuan (Global and Planetary Change, 2019)
The Tibetan Plateau and its surrounding mountains exhibit the largest concentration of glaciers at lower latitudes on earth, providing source water for the large river systems in Asia. However, glacier observations in this region are short and scarce and hence limit a better understanding of glacier behaviors under a warming climate and thereto coupled processes. The purpose of this research is to investigate the potential and the uncertainty for using pioneering trees on glacial deposits/glacier forefields as a proxy record for past glacier fluctuations in the Himalaya-Nyanqentanggula-Hengduan (H2N) area. It was found that Hippophae tibetana spent 4 years to colonize the glacier forefields at Hailuogou glacier and Pinus wallichiana germinated 11 years after glacier retreating at Gangapuna and Raikot glaciers. At deposit sites of glacier avalanche and glacial lake outburst, it took 8 years for Larix griffithii to germinate after the historical events. As shown by bootstrap resampling, the precision of the sampled maximum tree age could reach 2-14 years, which is related to the sample size to ensure the possibility of obtaining the eldest trees. However, if using the traditional sampling method at 100-cm height, errors of tree age estimation may reach up to +/- 20 years due to uncertainties of pith offset estimation and height-age calibration. If samples are collected with pith from <= 20 cm tree height, an error of < 5 years in tree age estimation could be derived. These results suggest that maximum tree ages may be a promising proxy record of glacier fluctuation with decadal precision in the H2N mountain range if the sample-collecting methods are rigidly controlled and the old trees are well replicated. The uncertainties due to the pith offset, tree height age and sample size imply that cautions should be taken when integrating exposure age dating on decadal-multidecadal glacier fluctuations at regional to hemispheric scales.
CRIS-Team WoS Importer:2019-02-21

Two Nothofagus Species in Southernmost South America Are Recording Divergent Climate Signals - Soto Rogel, Pamela; Carlos Aravena, Juan; Villalba, Ricardo; Bringas, Christian; Meier, Wolfgang; Gonzalez-Reyes, Alvaro; Grießinger, Jussi (Forests, 2022)
Recent climatic trends, such as warming temperatures, decrease in rainfall, and extreme weather events (e.g., heatwaves), are negatively affecting the performance of forests. In northern Patagonia, such conditions have caused tree growth reduction, crown dieback, and massive die-back events. However, studies looking at these consequences in the southernmost temperate forest (Nothofagus betuloides and Nothofagus pumilio) are much scarcer, especially in southernmost South America (SSA). These forests are also under the influence of the positive phase of Antarctic Oscillation (AAO, also known as Southern Annular Mode, SAM) that has been associated with increasing trends in temperature, drought, and extreme events in the last decades. This study evaluated the growth patterns and the climatic response of eight new tree-ring chronologies from Nothofagus species located at the upper treeline along different environmental gradients in three study areas: Punta Arenas, Yendegaia National Park, and Navarino Island in SSA. The main modes of the ring-width index (RWI) variation were studied using principal component analysis (PCA). We found that PC1 has the higher loadings for sites with precipitation values over 600 mm/yr, PC2 with N. betuloides sites, and PC3 with higher loadings for sites with precipitation values below 600 mm/yr. Our best growth-climate relationships are between N. betuloides and AAO and the most northeastern site of N. pumilio with relative humidity (which coincides with heatwaves and extreme drought). The climatic signals imprinted in the southernmost forests are sensitive to climatic variability, the climate forcing AAO, and the effects of climate change in the last decades.
CRIS-Team WoS Importer:2022-06-10

Unexpected climate variability inferred from a 380-year tree-ring earlywood oxygen isotope record in the Karakoram, Northern Pakistan - Zhu, Haifeng; Huang, Ru; Asad, Fayaz; Liang, Eryuan; Bräuning, Achim; Zhang, Xuezhen; Dawadi, Binod; Man, Wenmin; Grießinger, Jussi (Climate Dynamics, 2021)
To provide a long-term context for understanding the “Karakoram Anomaly” in recent glacier studies, we originally aimed to develop an annually resolved multi-century winter–spring precipitation record using tree-ring earlywood cellulose δ18O (δ18OEW) of Pinus wallachina from the Karakoram, northern Pakistan. Out of expectation, winter (January–May) temperature rather than precipitation is found to be the dominant climate signal (r = 0.63, p < 0.01, 1955–2013) stored in the δ18OEW chronology. Precipitation signals mainly appear at high-frequency variations, but weaker than temperature signal. We reconstructed January–May temperature back to 1631 with an explained variance of 39.7 % during the calibration period of 1955–2013. The reconstruction reveals that the Little Ice Age (LIA) was 0.94 °C warmer during 1647–1746 than the twentieth century (1900–1999). These warmer conditions are additionally validated by ice-core δ18O data from the Kunlun Mountains of High Asia and the northern North America. The eastward Polar Vortex and enhanced mid-latitude Westerlies on the Euro-Asia continent may be a possible explanation of a spatial coherency of LIA temperature between the Karakoram and the northern North America. Although not the original aim of this study, we provide evidence that the attribution of anomalous behavior of Karakoram glaciers in a long-term context may be misled when using precipitation reconstructions derived from tree-ring oxygen isotope.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Karakoram; Little Ice Age; Oxygen isotopes; Tree‐rings; Winter‐spring temperature reconstruction

Untersuchungen zur Klimavariabilität auf dem Tibetischen Plateau - Ein Beitrag auf der Basis stabiler Kohlenstoff- und Sauerstoffisotopen in Jahrringen von Bäumen waldgrenznaher Standorte. - Grießinger, Jussi (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2008)
UnivIS-Import:2016-07-26:Pub.2008.nat.dgeo.IG.zentr.unters

Variability of summer humidity during the past 800 years on the eastern Tibetan Plateau inferred from δ18O of tree-ring cellulose - Wernicke, Jakob; Grießinger, Jussi; Hochreuther, Philipp; Bräuning, Achim (Climate of the Past, 2015)

Variability of summer humidity during the past 800 years on the eastern Tibetan Plateau inferred from δ18O of tree-ring cellulose - Wernicke, Jakob; Grießinger, Jussi; Hochreuther, Philipp; Bräuning, Achim (Climate of the Past, 2015)
We present an 800-year δ18O chronology from the eastern part of the Tibetan Plateau (TP). The chronology dates back to AD 1193 and was sampled in AD 1996 from living Juniperus tibetica trees. This first long-term tree-ring-based δ18O chronology for eastern Tibet provides a reliable archive for hydroclimatic reconstructions. Highly significant correlations were obtained with hydroclimatic variables (relative humidity, vapour pressure, and precipitation) during the summer season. We applied a linear transfer model to reconstruct summer season relative humidity variations over the past 800 years. More moist conditions prevailed during the termination of the Medieval Warm Period while a systematic shift during the Little Ice Age is not detectable. A distinct trend towards more dry conditions since the 1870s is apparent. The moisture decline weakened around the 1950s but still shows a negative trend. The mid-19th century humidity decrease is in good accordance with several multiproxy hydroclimate reconstructions for south Tibet. However, the pronounced summer relative humidity decline is stronger on the central and eastern TP. Furthermore, the relative humidity at our study site is significantly linked to the relative humidity at large parts of the TP. Therefore, we deduce that the reconstructed relative humidity is mostly controlled by local and mesoscale climatic drivers, although significant connections to the higher troposphere of west-central Asia were observed.
Keywords: Climate variability; Oxygen isotopes; Tibetan plateau; Relative humidity

Water use strategies determine divergent growth trends of spruce and juniper on the southeastern Tibetan plateau - Wang, Lu; Liu, Hongyan; Shi, Liang; Zhang, Xianliang; Liang, Boyi; Huang, Ru; Grießinger, Jussi; Leavitt, Steven; Yue, Yuemin; Wang, Kelin (Forest Ecosystems, 2024)
Warming and increased CO2 levels are generally believed to enhance photosynthetic rates (A) and tree growth, especially in alpine treelines. However, this positive effect may be limited by moisture availability. Here we compare the radial growth and intrinsic water use efficiency (iWUE) of two widely-distributed evergreen needleleaf species, Tibetan juniper (Juniperus tibetica) and Balfour spruce (Picea balfouriana), at the same site near the treeline on the southeastern Tibetan Plateau using tree-ring width and dual isotopes (δ13C and δ18O). We observed that with a 70-ppm increase in atmospheric CO2 from 1954 to 2007, juniper radial growth was significantly stimulated, whereas spruce growth remained constant. Correlation analysis between tree-ring width and climate factors revealed that spruce was more moisture-sensitive than juniper. Although the increases in iWUE for juniper (22%) and spruce (26%) were similar, iWUE changes in spruce were more influenced by stomatal conductance (gs) rather than A, supporting that moisture availability inhibits spruce growth. Our study implies that predicting growth dynamics in alpine forests based on the growth-temperature relationship may be inadequate, as they are likely moisture-limited. It also suggests that increases in A may not be as widespread as previously thought, which helps improve forest productivity modeling.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Climate changes; Dual-isotope approach; Intrinsic water-use efficiency (iWUE); Tibetan plateau; Tree rings